Method for producing sulfide solid electrolyte
By replacing the original solvent with hydrocarbon solvents during the manufacturing process of sulfide solid electrolyte, the problems of increasing particle size and enlarging particle size distribution are solved by heating, and the ionic conductivity of the electrolyte is improved.
Patent Information
- Application Number
- CN202380050906.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-01-25
- Filing Date
- 2023-07-07
- Publication Date
- 2025-02-14
AI Technical Summary
In the prior art, when manufacturing sulfide solid electrolytes, the particle size increases and the particle size distribution expands due to heating, which in turn affects the ionic conductivity of the electrolyte.
By mixing the raw materials in the first solvent, an electrolyte precursor is obtained, which is then contacted with a hydrocarbon solvent different from the first solvent, and heated to avoid granulation caused by solvent residue.
The control of particle size and the inhibition of particle size distribution are achieved, and the ionic conductivity of the sulfide solid electrolyte is improved.
Smart Images

Figure BDA0005217663510000461 
Figure BDA0005217663510000481 
Figure BDA0005217663510000511
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing a sulfide solid electrolyte. Background Art
[0002] In recent years, with the rapid popularization of information-related devices or communication devices such as personal computers, cameras and mobile phones, the development of batteries used as their power sources has also received attention. In the past, in batteries used for such purposes, electrolytes containing flammable organic solvents were used, but by making the battery fully solid, the safety device is simplified because no flammable organic solvent is used in the battery, and the manufacturing cost and productivity are excellent. Therefore, the development of batteries in which the electrolyte is replaced by a solid electrolyte layer is carried out.
[0003] As a method for manufacturing a solid electrolyte for a solid electrolyte layer, it is roughly divided into a solid phase method and a liquid phase method, and the liquid phase method includes a uniform method in which a solid electrolyte material is completely dissolved in a solvent, and an inhomogeneous method in which a solid electrolyte material is not completely dissolved but a suspension coexists with solid and liquid. For example, as a uniform method in the liquid phase method, a method of dissolving a solid electrolyte in a solvent to reprecipitate it is known (for example, refer to patent document 1), and as an inhomogeneous method, a method of reacting raw materials such as lithium sulfide in a solvent containing a polar aprotic solvent is known (for example, refer to patent documents 2 and 3), and a method for manufacturing a solid electrolyte using a specific compound having an amino group as a complexing agent (for example, refer to patent documents 4 and 5). Non-patent document 1 records: using tetrahydrofuran and ethanol, a tetrahydrofuran-ethanol precursor solution of Li6PS5Br is prepared, which is dried and heated, thereby preparing a solid electrolyte having a argyrodite-type crystal structure and the argyrodite-type crystal structure having a composition of Li6PS5Br.
[0004] Non-patent documents 2 and 3 describe that Li2S, P2S5 and S (7:3:x (x=3, 5 and 7) molar ratio) are added to a mixed solvent (1:1:0.05 (volume ratio)) of acetonitrile, tetrahydrofuran and ethanol to generate lithium polysulfide and highly reactive sulfur radicals, and after stirring for several minutes, the mixture is dried under vacuum and heated at a heating temperature of 270°C, 350°C, etc. to produce Li7P3S 11 A crystalline solid electrolyte with a composition of
[0005] In addition, there are also known methods for producing a sulfide solid electrolyte by contacting a mixture containing an alkali metal sulfide and sulfur with a sulfur compound such as phosphorus sulfide (for example, refer to Patent Document 6); a sulfide solid electrolyte obtained by mixing Li2S and P2S5 in an organic solvent such as tetrahydrofuran and dimethoxyethane and precipitating them (for example, refer to Patent Document 7); a method for producing a solid electrolyte by supplying a liquid containing raw materials containing lithium, phosphorus, sulfur and chlorine and a solvent such as ethanol to a liquid or gas having a temperature higher than the boiling point of the solvent, evaporating the solvent, and reacting the raw materials to precipitate an argyrodite-type crystal structure (for example, refer to Patent Document 8), etc.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2014-191899
[0009] Patent Document 2: International Publication No. 2014 / 192309
[0010] Patent Document 3: International Publication No. 2018 / 054709
[0011] Patent Document 4: International Publication No. 2020 / 105737
[0012] Patent Document 5: International Publication No. 2021 / 230189
[0013] Patent Document 6: Japanese Patent Application Publication No. 2014-220051
[0014] Patent Document 7: Japanese Patent Application Publication No. 2015-232965
[0015] Patent Document 8: Japanese Patent Application Publication No. 2019-169459
[0016] Non-patent literature
[0017] Non-patent document 1: J. Mater. Chem. A, 2019, 7, 558-566
[0018] Non-patent document 2: 62nd Battery Symposium Draft Paper, published on November 29, 2021, All-solid-state batteries / sulfide electrolytes, 3E01
[0019] Non-patent literature 3: Adv. Energy Sustenability Res., 2022, 2200019 Summary of the invention
[0020] Technical problem to be solved by the invention
[0021] The present invention has been made in view of the above circumstances, and an object of the present invention is to efficiently provide a sulfide solid electrolyte having high ion conductivity in which an increase in particle size and a widening of particle size distribution are suppressed.
[0022] Solutions for solving the above technical problems
[0023] The method for producing the sulfide solid electrolyte of the present invention is:
[0024] A method for manufacturing a sulfide solid electrolyte, comprising:
[0025] A raw material containing a plurality of raw materials is mixed in a first solvent to obtain a solution containing an electrolyte precursor, wherein the raw material contains at least one atom selected from lithium atoms, phosphorus atoms, sulfur atoms, and halogen atoms;
[0026] removing the solvent from the solution to obtain an electrolyte precursor;
[0027] contacting the electrolyte precursor with a second solvent; and
[0028] Then heating,
[0029] The second solvent is different from the first solvent and is a hydrocarbon solvent.
[0030] Effects of the Invention
[0031] According to the present invention, it is possible to efficiently provide a sulfide solid electrolyte having high ion conductivity with suppressed increase in particle size and widening of particle size distribution. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is the X-ray diffraction spectrum of the powder obtained in Example 1.
[0033] Figure 2 This is the X-ray diffraction spectrum of the powder obtained in Example 2.
[0034] Figure 3 This is the X-ray diffraction spectrum of the powder obtained in Example 3.
[0035] Figure 4 This is the X-ray diffraction spectrum of the powder obtained in Example 4.
[0036] Figure 5 This is the X-ray diffraction spectrum of the powder obtained in Example 5.
[0037] Figure 6 This is the X-ray diffraction spectrum of the powder obtained in Comparative Example 1.
[0038] Figure 7 This is the X-ray diffraction spectrum of the powder obtained in Example 6.
[0039] Figure 8 This is the X-ray diffraction spectrum of the powder obtained in Comparative Example 2.
[0040] Fig. 9 This is the X-ray diffraction spectrum of the powder obtained in Example 7.
[0041] Fig.10 This is the X-ray diffraction spectrum of the powder obtained in Example 8.
[0042] Fig.11 This is the X-ray diffraction spectrum of the powder obtained in Comparative Example 3. DETAILED DESCRIPTION
[0043] Hereinafter, an embodiment of the present invention (hereinafter sometimes referred to as "the present embodiment") is described. In addition, in this specification, the upper and lower limit values involved in the numerical ranges of "above", "below", and "to" are values that can be arbitrarily combined, and the values of the embodiments can also be used as the upper and lower limit values. In addition, preferred provisions can be adopted arbitrarily. That is, a preferred provision can be combined with another preferred provision or multiple provisions. It can be said that the combination of preferred provisions is more preferred.
[0044] (Discovery made by the present inventors to complete the present invention)
[0045] The present inventors have conducted intensive studies to solve the above-mentioned technical problems and, as a result, have found the following matters and completed the present invention.
[0046] In recent years, with the goal of practical application of all-solid-state batteries, the liquid phase method has attracted attention as a method that can be synthesized simply and in large quantities in addition to versatility and applicability. As a solid phase method, a method represented by a mechanical grinding method can be cited, in which the raw materials are crushed and mixed with a pulverizer and reacted to obtain a solid electrolyte, but due to the high cost of equipment and the need for a large amount of initial investment, it is difficult to reduce costs.
[0047] On the other hand, in the method for producing a sulfide solid electrolyte based on a liquid phase method disclosed in the above patent documents and non-patent documents, granulation sometimes occurs due to heating at high temperature during crystallization, and the particle size becomes larger. Therefore, when the obtained sulfide solid electrolyte is used for the production of lithium ion batteries, it is necessary to adjust the particle size in advance, which has the problem of reduced production efficiency. In this way, in the production of sulfide solid electrolytes, it is necessary to study not only the production efficiency based on the reaction promotion of raw materials, but also the production efficiency in the production of lithium ion batteries after obtaining the sulfide solid electrolyte.
[0048] The present inventors have focused on the fact that, in the above patent documents and non-patent documents that disclose the liquid phase method, when heating is used for crystallization, there is no mention of the problem of granulation and enlargement of particle size caused by the heating. In addition, in the case of obtaining a sulfide solid electrolyte having an argyrodite-type crystal structure, it can be seen from the production method disclosed in Patent Document 8, for example, that heating at a high temperature of about 430° C. is inevitable. Therefore, the tendency that granulation is more likely to occur and the particle size is more likely to increase becomes significant.
[0049] The present inventors have studied the situation that granulation and particle size increase due to heating, and found that granulation due to heating is affected by the residual solvent used in the reaction of the raw materials. It is known that this tendency is more significant when tetrahydrofuran, ethanol, or a solvent called a complexing agent having a nitrogen atom, which is also used in the above-mentioned patent document, is used.
[0050] Thus, it was found that in the case of a liquid phase method, i.e., a reaction of raw materials in a solution, if heating for crystallization is performed while the solvent used still remains, the bonding force between particles increases due to the remaining solvent, and granulation due to aggregation becomes easy to occur. Therefore, the present inventors have found that when an electrolyte precursor obtained by removing the solvent from a solution in which raw materials are mixed in a solvent is brought into contact with a solvent different from the solvent, the sulfide solid electrolyte obtained by subsequent heating does not granulate, and the increase in particle size and the expansion of particle size distribution are suppressed.
[0051] (Various Aspects of the Present Embodiment)
[0052] The method for producing a sulfide solid electrolyte according to the first aspect of the present embodiment is as follows:
[0053] A method for manufacturing a sulfide solid electrolyte, comprising:
[0054] A raw material containing a plurality of raw materials is mixed in a first solvent to obtain a solution containing an electrolyte precursor, wherein the raw material contains at least one atom selected from lithium atoms, phosphorus atoms, sulfur atoms, and halogen atoms;
[0055] removing the solvent from the solution to obtain an electrolyte precursor;
[0056] contacting the electrolyte precursor with a second solvent; and
[0057] Then heating,
[0058] The second solvent is different from the first solvent and is a hydrocarbon solvent.
[0059] In the method for producing a sulfide solid electrolyte of the present embodiment, the raw material contents are mixed in the first solvent, thereby adopting a liquid phase method. Therefore, the production method of the present embodiment can produce a sulfide solid electrolyte extremely efficiently.
[0060] The manufacturing method of this embodiment includes mixing the raw material content in the first solvent to obtain a solution containing an electrolyte precursor. That is, as the first solvent, a solvent that can dissolve the raw materials contained in the raw material content and the reactants generated by these raw materials can be used. By dissolving in the solvent in this way, the raw materials contained in the raw material content react with each other rapidly, so that a sulfide solid electrolyte can be obtained extremely efficiently.
[0061] Here, the "electrolyte precursor" refers to the precursor of the sulfide solid electrolyte obtained by the production method of the present embodiment, and is different from the raw material contained in the raw material content and the sulfide solid electrolyte obtained by heating. More specifically, it is a product obtained by the reaction of the raw material provided for mixing and the first solvent when obtaining a solution containing the electrolyte precursor in the production method of the present embodiment.
[0062] The presence of the "electrolyte precursor" can be confirmed by, for example, analyzing the "electrolyte precursor" using FT-IR (diffuse reflectance) and detecting a peak different from that of the raw material and the sulfide solid electrolyte, or by detecting the same peak through powder X-ray diffraction (XRD) measurement.
[0063] In the manufacturing method of this embodiment, the solute dissolved in the solution, i.e., the electrolyte precursor, is obtained by removing the solvent from the solution obtained by the above-mentioned mixing. Then, the obtained electrolyte precursor is contacted with the second solvent. Here, as the second solvent, by using a solvent that is different from the first solvent and is a hydrocarbon solvent, the first solvent attached to the electrolyte precursor can be washed and removed.
[0064] Then, the electrolyte precursor is heated together with the second solvent. By heating, the electrolyte precursor can generate an amorphous sulfide solid electrolyte or a crystalline sulfide solid electrolyte depending on the heating conditions.
[0065] Here, the first solvent attached to the electrolyte precursor is replaced by the second solvent which is a hydrocarbon solvent, and is thus removed by volatilization or combustion by heating. Therefore, even if the electrolyte precursor is heated, granulation caused by the residual solvent and heating will not occur. In addition, the first solvent that contributes to the formation of the electrolyte precursor is removed from the structure of the electrolyte precursor, and reactions such as decomposition of the electrolyte precursor are performed, and the electrolyte precursor becomes a sulfide solid electrolyte. In this way, according to the manufacturing method of this embodiment, a sulfide solid electrolyte in which the increase in particle size and the expansion of particle size distribution are suppressed can be efficiently provided.
[0066] A method for producing a sulfide solid electrolyte according to a second aspect of the present embodiment is, in the above-mentioned first aspect,
[0067] The hydrocarbon solvent is at least one organic solvent selected from aliphatic hydrocarbon solvents, alicyclic hydrocarbon solvents, and aromatic hydrocarbon solvents.
[0068] If the hydrocarbon solvent used as the second solvent is at least one organic solvent selected from aliphatic hydrocarbon solvents, alicyclic hydrocarbon solvents and aromatic hydrocarbon solvents, the first solvent attached to the electrolyte precursor can be more easily washed and removed, thereby more efficiently obtaining a sulfide solid electrolyte in which the increase in particle size and the expansion of particle size distribution are suppressed.
[0069] A method for producing a sulfide solid electrolyte according to a third aspect of the present embodiment is, in the first or second aspect,
[0070] The solubility of the lithium halide in the hydrocarbon solvent at 25° C. is 0.5 mass % or less.
[0071] In the manufacturing method of this embodiment, it is preferred to use a hydrocarbon solvent with a low solubility of lithium halide, so that the solubility of lithium halide relative to the hydrocarbon solvent of the second solvent at 25° C. is 0.5% by mass or less. If such a hydrocarbon solvent is used, the lithium atoms and halogen atoms contained in the electrolyte precursor will not be taken into the second solvent and can be retained in the electrolyte precursor. Therefore, not only can the first solvent be cleaned and removed, but also more lithium atoms and halogen atoms supplied as raw materials can be retained in the electrolyte precursor, so that the ion conductivity is improved.
[0072] A fourth method for producing a sulfide solid electrolyte according to the present embodiment is, in any one of the first to third methods,
[0073] The hydrocarbon solvent is an aromatic hydrocarbon solvent,
[0074] The fifth embodiment of the method for producing a sulfide solid electrolyte is, in the fourth embodiment,
[0075] The aromatic hydrocarbon solvent is alkylbenzene,
[0076] The sixth embodiment of the method for producing a sulfide solid electrolyte is, in the fifth embodiment,
[0077] The alkylbenzene has an alkyl group having 1 to 4 carbon atoms.
[0078] The second solvent is an aromatic hydrocarbon solvent, and among them, if it is an alkylbenzene, especially an alkylbenzene having an alkyl group with 1 to 4 carbon atoms, the effect of using the second solvent can be more efficiently obtained.
[0079] A seventh method for producing a sulfide solid electrolyte according to the present embodiment is, in any one of the first to sixth methods,
[0080] The amount of the second solvent used in the contacting is 50 parts by mass or more and 10,000 parts by mass or less relative to 100 parts by mass of the electrolyte precursor.
[0081] By setting the usage amount of the second solvent to be within the above range, the effect of using the second solvent can be obtained more efficiently.
[0082] An eighth aspect of the present embodiment is a method for producing a sulfide solid electrolyte, in any one of the first to seventh aspects,
[0083] The contacting is performed at least once.
[0084] In the manufacturing method of this embodiment, the contact may be performed once or twice or more, and the contact may be appropriately determined according to needs.
[0085] A ninth aspect of the present embodiment is a method for producing a sulfide solid electrolyte, in any one of the first to eighth aspects,
[0086] The raw material contains elemental sulfur.
[0087] It is considered that when elemental sulfur is used as a raw material, for example, by using it in combination with a raw material containing lithium atoms such as lithium sulfide, elemental sulfur reacts with a raw material containing lithium atoms such as lithium sulfide in a solvent to form lithium polysulfide, generating sulfur free radicals. Sulfur free radicals are highly reactive, and by promoting reactions with other raw materials such as phosphorus pentasulfide and other raw materials containing halogen atoms, soluble polysulfides (hereinafter also referred to as "polysulfides"), which are precursors of sulfide solid electrolytes, i.e., electrolyte precursors, are generated. By decomposing the polysulfide by heating or the like, a sulfide solid electrolyte with improved ion conductivity can be efficiently manufactured.
[0088] By using a raw material containing elemental sulfur as a raw material, mixing it in a first solvent, a soluble polysulfide is generated as an electrolyte precursor. Then, by heating, the polysulfide is decomposed to become an amorphous sulfide solid electrolyte or a crystalline sulfide solid electrolyte, and the crystallinity of the crystalline sulfide solid electrolyte is improved. Here, by contacting the electrolyte precursor (polysulfide) with the second solvent before heating, the first solvent attached to the electrolyte precursor can be washed and removed. Therefore, even if the electrolyte precursor (polysulfide) is heated, granulation caused by heating due to residual solvent does not occur, and a sulfide solid electrolyte in which the increase in particle size and the expansion of particle size distribution are suppressed can be provided.
[0089] When using a raw material containing elemental sulfur, heating is mainly performed for decomposition of polysulfides, removal of solvents and crystallization. In addition, the removal of elemental sulfur generated by decomposition of polysulfides can also be performed by evaporation by heating, but methods other than heating such as solvent washing and hydrodesulfurization can also be applied.
[0090] A method for producing a sulfide solid electrolyte according to a tenth aspect of the present embodiment is, in the ninth aspect,
[0091] The first solvent is an organic solvent containing at least one atom selected from oxygen atoms and nitrogen atoms,
[0092] The eleventh embodiment of the method for producing a sulfide solid electrolyte is, in the tenth embodiment,
[0093] The organic solvent includes at least one organic solvent selected from alcohol solvents, ether solvents, and nitrile solvents.
[0094] The second solvent is different from the first solvent and is a hydrocarbon solvent. Therefore, in terms of the relationship with the second solvent, it is preferred to use a solvent containing at least one atom selected from oxygen atoms and nitrogen atoms, i.e., an atom called a heteroatom, as the first solvent. If such a first solvent is used, the generation of sulfur free radicals is promoted through the reaction of elemental sulfur and lithium sulfide to form lithium polysulfide. Since sulfur free radicals are highly reactive, they act on other raw materials such as phosphorus pentasulfide and other raw materials containing halogen atoms, and react with lithium sulfide or lithium polysulfide, thereby promoting the generation of soluble polysulfides. This soluble polysulfide is a precursor of a sulfide solid electrolyte. By heating, the polysulfide is decomposed and quickly becomes an amorphous sulfide solid electrolyte or a crystalline sulfide solid electrolyte, and the crystallinity of the crystalline sulfide solid electrolyte is improved. As a result, a sulfide solid electrolyte with few impurities and high ionic conductivity can be efficiently obtained.
[0095] In addition, as such a solvent containing heteroatoms, at least any one of an alcohol solvent, an ether solvent and a nitrile solvent is preferably used. By using these solvents, the effect of using the above-mentioned solvent containing heteroatoms, i.e. the generation of free radicals of sulfur and the formation of electrolyte precursors (polysulfides) are promoted. In addition, by using alcohol solvents, ether solvents and nitrile solvents, the generation of free radicals of sulfur and the formation of electrolyte precursors (polysulfides) are promoted in a balanced manner. As a result, a sulfide solid electrolyte with few impurities and high ionic conductivity can be efficiently obtained.
[0096] A twelfth aspect of the present embodiment is a method for producing a sulfide solid electrolyte, in any one of the ninth to eleventh aspects,
[0097] The heating temperature during the heating is 20° C. or higher and 500° C. or lower.
[0098] As described above, in the manufacturing method of the present embodiment, by heating, the electrolyte precursor can generate an amorphous sulfide solid electrolyte and then generate a crystalline sulfide solid electrolyte according to the heating conditions. Here, in the case where the raw material content includes elemental sulfur, the electrolyte precursor (polysulfide) is generated as described above. Therefore, in the case where the raw material content includes elemental sulfur, heating not only generates the above-mentioned amorphous sulfide solid electrolyte and then generates a crystalline sulfide solid electrolyte, but also includes decomposition of the electrolyte precursor (polysulfide). If the heating temperature during heating is within the above range, more efficient and reliable decomposition and crystallization of the electrolyte precursor (polysulfide) can be performed.
[0099] A thirteenth aspect of the present embodiment is a method for producing a sulfide solid electrolyte, in any one of the ninth to twelfth aspects,
[0100] The amount of the elemental sulfur used is 0.5 mol or more relative to 1.0 mol of the lithium sulfide.
[0101] The amount of elemental sulfur used relative to lithium sulfide can be adopted without particular limitation, but it is preferably used in an amount of a certain amount or more such as 0.5 mol or more relative to 1.0 mol of lithium sulfide. This amount is an excess amount compared to the sulfur atoms required for the desired sulfide solid electrolyte, and the details will be described later. In this way, by using an excess amount of elemental sulfur, the generation of the above-mentioned sulfur radicals is promoted, so that as a result, a sulfide solid electrolyte with improved ion conductivity can be efficiently produced.
[0102] A fourteenth aspect of the present embodiment is a method for producing a sulfide solid electrolyte, wherein in any one of the first to eighth aspects,
[0103] The raw material contains lithium sulfide, phosphorus sulfide and at least one halogen atom-containing raw material selected from lithium halide and elemental halogen,
[0104] A fifteenth aspect of the method for producing a sulfide solid electrolyte is, in any one of the first to ninth aspects,
[0105] The raw material contains no elemental sulfur.
[0106] In the manufacturing method of the present embodiment, as a raw material content other than the raw material content containing elemental sulfur in the ninth embodiment, a raw material content containing lithium sulfide, phosphorus sulfide, and at least one halogen atom-containing raw material selected from lithium halide and elemental halogen is preferably used. In the manufacturing method of the present embodiment, even if an electrolyte precursor using various raw material contents is used, a sulfide solid electrolyte in which the increase in particle size and the expansion of particle size distribution are suppressed can be efficiently provided. That is, in the manufacturing method of the present embodiment, it is extremely important to contact the electrolyte precursor with the second solvent.
[0107] It can be said that according to the manufacturing method of this embodiment, as long as the electrolyte precursor is obtained by mixing the above-mentioned raw material content and the first solvent, no matter what kind of electrolyte precursor it is, by contacting the electrolyte precursor with the second solvent, the effect of efficiently providing a sulfide solid electrolyte with an increase in particle size and a suppressed expansion of particle size distribution can be obtained.
[0108] A method for producing a sulfide solid electrolyte according to a sixteenth aspect of the present embodiment is, in the fourteenth or fifteenth aspect,
[0109] The method comprises: before the heating, heating the electrolyte precursor while supplying hydrogen sulfide,
[0110] A seventeenth aspect of the present embodiment is a method for producing a sulfide solid electrolyte, wherein in any one of the fourteenth to sixteenth aspects,
[0111] The first solvent includes an alcohol solvent and an ether solvent.
[0112] When a raw material containing lithium sulfide, phosphorus sulfide, and at least one halogen atom-containing raw material selected from lithium halide and elemental halogen is used as a raw material containing material, and further a raw material containing material not containing elemental sulfur is used, it is particularly effective to heat the electrolyte precursor while supplying hydrogen sulfide. In addition, in this case, as the first solvent, it is preferred to include an alcohol solvent and an ether solvent. By using such a solvent, it is easy to obtain an electrolyte precursor, so a sulfide solid electrolyte can be obtained more efficiently.
[0113] The electrolyte precursor is formed by mixing the raw material content in the first solvent, but sometimes a part of the raw material contained in the raw material content exists in the state of the raw material. For example, when lithium sulfide (Li2S) is used as the raw material, sometimes the lithium sulfide (Li2S) exists in the original state. The solvent containing oxygen atoms such as the alcohol solvent preferably used in the manufacturing method of the present embodiment is easy to obtain the electrolyte precursor as described above, and is excellent in that the residual raw material can be reduced. On the other hand, due to the high reactivity, it is easy to react with lithium sulfide to generate lithium alcohol such as lithium ethanol, and sometimes the lithium sulfide that can react with other raw materials becomes unhelpful for the reaction with other raw materials. Moreover, if the lithium alcohol remains as it is, the purity of the sulfide solid electrolyte is reduced, and sometimes the lithium alcohol is carbonized and remains by firing, resulting in a reduction in quality such as a reduction in ionic conductivity.
[0114] In this way, when a solvent including an alcohol solvent and an ether solvent is used as the first solvent, lithium alcoholate is sometimes generated together with the electrolyte precursor. Here, by heating the electrolyte precursor while supplying hydrogen sulfide, the remaining lithium alcoholate can be converted into lithium sulfide (Li2S). Specifically, it is considered that the following reactions (1) to (3) occur.
[0115] Li2S+EtOH→EtOLi+LiSH (1)
[0116] 2LiSH→Li2S+H2S (2)
[0117] 2EtOLi+H2S→Li2S+2EtOH (3)
[0118] The above reaction assumes the case where lithium sulfide (Li2S) is used as a raw material and ethanol (EtOH) is used as an alcohol solvent of the first solvent. If lithium sulfide (Li2S) exists in a state as it is, it reacts with ethanol to generate lithium ethoxide (LiOEt) and lithium hydrosulfide (LiSH) as shown in reaction formula (1). Lithium hydrosulfide (LiSH) decomposes as shown in reaction formula (2) to generate lithium sulfide (Li2S) and hydrogen sulfide.
[0119] As shown in reaction formula (3), the lithium ethoxide (LiOEt) generated in reaction formula (1) reacts with hydrogen sulfide generated in reaction formula (2) and hydrogen sulfide supplied separately to generate lithium sulfide (Li2S). The lithium sulfide (Li2S) generated by reaction formula (3) sometimes reacts with other raw materials to form a sulfide solid electrolyte, and even if it remains as it is, it does not cause the ion conductivity of the sulfide solid electrolyte to decrease. In this way, by supplying hydrogen sulfide while performing heat treatment, it is possible to suppress the residue of impurities such as lithium ethoxide and the loss of raw materials, thereby improving the quality of the sulfide solid electrolyte.
[0120] Furthermore, in the manufacturing method of this embodiment, since the electrolyte precursor is brought into contact with the second solvent, the first solvent attached to the surface of the electrolyte precursor can be removed, and thus impurities such as lithium alkoxide can also be removed. Therefore, in addition to the original effect of suppressing the increase in particle size and the expansion of particle size distribution, the remaining impurities such as lithium alkoxide and the loss of raw materials can be further suppressed, and the quality of the sulfide solid electrolyte can be further improved.
[0121] The method for producing a sulfide solid electrolyte according to an eighteenth aspect of the present embodiment is, in the seventeenth aspect,
[0122] When obtaining the solution containing the electrolyte precursor, the raw material-containing substances are mixed in an ether solvent, and then an alcohol solvent is added and mixed.
[0123] As described above, as the first solvent, a solvent containing an alcohol solvent and an ether solvent can be used, a mixed solvent containing an alcohol solvent and an ether solvent can be used together, or an alcohol solvent and an ether solvent can be used in stages as in the eighteenth aspect.
[0124] Hereinafter, in the description of the eighteenth aspect, the solvent that is first mixed with the raw material content in the first solvent is referred to as the 1-1 solvent, and the solvent that is used next is referred to as the 1-2 solvent.
[0125] The eighteenth embodiment is a embodiment in which, when a solvent including an alcohol solvent and an ether solvent is used as the first solvent, an ether solvent is used as the 1-1 solvent and an alcohol solvent is used as the 1-2 solvent. That is, the preferred order of use of the alcohol solvent and the ether solvent when the solvent including an alcohol solvent and an ether solvent is used as the first solvent is specified.
[0126] In the manufacturing method using the liquid phase method, it is preferred that lithium sulfide, other phosphorus pentasulfide, and raw materials containing halogen atoms such as lithium bromide, lithium iodide, and lithium chloride are not separated in the liquid phase and contribute to the formation of the electrolyte precursor. As described above, the use of an alcohol solvent as the first solvent is effective in promoting the formation of the electrolyte precursor, but due to its high reactivity, lithium sulfide is easily converted into lithium alcohol. In addition, it is known that the reactivity is also high, especially with raw materials containing halogen atoms. In this way, when the first solvent is a solvent containing an ether solvent and an alcohol solvent, it is easy to separate and lose part of the raw materials.
[0127] In the eighteenth embodiment, an ether solvent is first used as the first solvent to prepare a mixture with the raw material content, that is, the mixture is prepared without completely dissolving the raw material content. The raw material content is not completely dissolved in the first solvent, so the reaction is slow, and the solvent and the raw material form a bond state based on a certain force (intermolecular force and chemical bond, etc.). In particular, the loose bond state with the solvent can suppress the loss of the raw material.
[0128] Next, the mixture is mixed with the first-second solvent to obtain a solution containing an electrolyte precursor. As described above, in the mixture, each raw material contained in the raw material content is maintained in a state of bonding with each other and the solvent, and by mixing it with the first-second solvent, it is dissolved while maintaining a loose bond with the first-first solvent, thereby obtaining a solution in which an electrolyte precursor is dissolved.
[0129] Here, the raw materials are supplied to the 1-2 solvent in a state where the raw materials are bound to each other and then loosely bound to the 1-1 solvent, thereby forming an electrolyte precursor without separation and loss caused by the reaction between the 1-2 solvent and the raw materials, thereby contributing to the formation of a sulfide solid electrolyte. For example, as described above, even when phosphorus sulfide (such as phosphorus pentasulfide (P2S5)) is used as a raw material, the dissolution and reaction of phosphorus sulfide and its reactants in the 1-2 solvent can be suppressed, thereby contributing to the formation of a sulfide solid electrolyte without separation and loss of phosphorus sulfide.
[0130] By using the 1-1 solvent and the 1-2 solvent separately in this manner, it is possible to suppress the separation and loss of various raw materials such as lithium sulfide, phosphorus sulfide, and lithium halide that are preferably used as raw materials.
[0131] A method for producing a sulfide solid electrolyte according to a nineteenth aspect of the present embodiment is, in any one of the fourteenth to eighteenth aspects,
[0132] The heating temperature during the heating is 150° C. or higher.
[0133] When the raw material content includes lithium sulfide, phosphorus sulfide and at least one halogen atom-containing raw material selected from lithium halide and elemental halogen, heating at the above heating temperature can more efficiently generate an amorphous sulfide solid electrolyte and further generate a crystalline sulfide solid electrolyte.
[0134] A twentieth aspect of the present embodiment is a method for producing a sulfide solid electrolyte, in any one of the first to nineteenth aspects,
[0135] The halogen atom is at least one atom selected from a chlorine atom, a bromine atom, and an iodine atom.
[0136] If the sulfide solid electrolyte contains halogen atoms, it has high ion conductivity. Among the halogen atoms, by containing at least one halogen atom selected from chlorine atoms, bromine atoms, and iodine atoms, it is easy to form an argyrodite-type crystal structure and a sulfide crystal lithium superion conductor region type II crystal structure that show particularly high ion conductivity.
[0137] A method for producing a sulfide solid electrolyte according to a twenty-first aspect of the present embodiment is, in the first to twentieth aspects,
[0138] A crystalline sulfide solid electrolyte having an argyrodite-type crystal structure or a sulfide crystalline lithium superion conductor region-type II crystal structure is produced.
[0139] In the production method of the present embodiment, a desired sulfide solid electrolyte can be produced by changing the types and blending ratios of the raw materials contained in the raw material content. Crystalline sulfide solid electrolytes having an argyrodite-type crystal structure and crystalline sulfide solid electrolytes having a sulfide crystalline lithium superion conductor region II-type crystal structure are known to be sulfide solid electrolytes having extremely high ion conductivity, and are preferred as the sulfide solid electrolytes intended to be obtained by the production method of the present embodiment.
[0140] (Sulfide solid electrolyte)
[0141] In this specification, "solid electrolyte" refers to an electrolyte that remains solid at 25° C. in a nitrogen atmosphere. The sulfide solid electrolyte in this embodiment is a solid electrolyte containing at least one atom selected from lithium atoms, phosphorus atoms, sulfur atoms, and halogen atoms, and preferably having ion conductivity caused by lithium atoms.
[0142] The “sulfide solid electrolyte” includes both an amorphous sulfide solid electrolyte and a crystalline sulfide solid electrolyte.
[0143] In this specification, the crystalline sulfide solid electrolyte refers to a sulfide solid electrolyte in which a peak derived from a solid electrolyte is observed in an X-ray diffraction pattern in an X-ray diffraction measurement, and is a material that is independent of the presence or absence of a peak derived from a raw material of the sulfide solid electrolyte. That is, the crystalline sulfide solid electrolyte includes a crystal structure derived from a solid electrolyte, and a part of it may be a crystal structure derived from the solid electrolyte, or all of it may be a crystal structure derived from the solid electrolyte. Furthermore, as long as the crystalline sulfide solid electrolyte has the above-mentioned X-ray diffraction pattern, a part of it may also include an amorphous sulfide solid electrolyte. Therefore, the crystalline sulfide solid electrolyte includes so-called glass ceramics obtained by heating an amorphous sulfide solid electrolyte to a crystallization temperature or higher.
[0144] In this specification, an amorphous sulfide solid electrolyte means an X-ray diffraction pattern having a halo pattern in which substantially no peaks other than peaks derived from the material are observed in X-ray diffraction measurement, regardless of the presence or absence of peaks derived from the raw material of the sulfide solid electrolyte.
[0145] [Method for producing sulfide solid electrolyte]
[0146] The method for producing the sulfide solid electrolyte of the present embodiment is as follows:
[0147] A method for manufacturing a sulfide solid electrolyte, comprising:
[0148] A raw material containing a plurality of raw materials is mixed in a first solvent to obtain a solution containing an electrolyte precursor, wherein the raw material contains at least one atom selected from lithium atoms, phosphorus atoms, sulfur atoms, and halogen atoms;
[0149] removing the solvent from the solution to obtain an electrolyte precursor;
[0150] contacting the electrolyte precursor with a second solvent; and
[0151] Then heating,
[0152] The second solvent is different from the first solvent and is a hydrocarbon solvent.
[0153] As described above, according to the manufacturing method of the present embodiment, if the electrolyte precursor is brought into contact with the second solvent, then as long as the electrolyte precursor is obtained by mixing the above-mentioned raw material content with the first solvent, no matter what kind of electrolyte precursor, the effect of efficiently providing a sulfide solid electrolyte with an increase in particle size and a suppressed expansion of particle size distribution can be obtained. Thus, in the manufacturing method of the present embodiment, it is extremely important to bring the electrolyte precursor into contact with the second solvent, so the description will start from the contact.
[0154] [Contacting the electrolyte precursor with the second solvent]
[0155] The manufacturing method of this embodiment includes: contacting the electrolyte precursor obtained when obtaining the solution containing the electrolyte precursor with the second solvent. As described above, granulation due to heating caused by the residue of the first solvent does not occur, and the increase of the particle size and the expansion of the particle size distribution can be suppressed to provide a sulfide solid electrolyte.
[0156] (Second solvent)
[0157] The second solvent used in the production method of this embodiment needs to be different from the first solvent and be a hydrocarbon solvent. By using such a second solvent, granulation due to heating caused by the residue of the first solvent does not occur, and a sulfide solid electrolyte can be provided in which the increase in particle size and the expansion of particle size distribution are suppressed.
[0158] Preferred examples of the hydrocarbon solvent as the second solvent include hydrocarbon solvents such as aliphatic hydrocarbon solvents, alicyclic hydrocarbon solvents and aromatic hydrocarbon solvents.
[0159] More specifically, representative and preferred examples include: aliphatic hydrocarbon solvents such as hexane, pentane, 2-ethylhexane, heptane, octane, decane, undecane, dodecane, and tridecane; alicyclic hydrocarbon solvents such as cyclohexane and methylcyclohexane; and aromatic hydrocarbon solvents such as benzene, toluene, xylene, mesitylene, ethylbenzene, and tert-butylbenzene.
[0160] Among the above hydrocarbon solvents, aromatic hydrocarbon solvents are preferred, and alkylbenzenes such as toluene, xylene, mesitylene, ethylbenzene, and tert-butylbenzene are more preferred. The carbon number of the alkyl group of the alkylbenzene is preferably 1 or more, and the upper limit is preferably 4 or less, more preferably 3 or less, and further preferably 2 or less. Here, the carbon number of the above alkyl group is the carbon number of one alkyl group, and in the case of having multiple alkyl groups, it is preferred to have multiple alkyl groups having the above carbon number.
[0161] In the production method of the present embodiment, the above-mentioned hydrocarbon solvents can be used alone or in combination of two or more.
[0162] In addition, the hydrocarbon solvent as the second solvent preferably has a property that the solubility of the lithium halide at 25° C. is 0.5 mass % or less. If the solubility of the lithium halide at 25° C. of the hydrocarbon solvent is as low as within the above range, the lithium atoms and halogen atoms contained in the electrolyte precursor will not be taken into the second solvent but can be retained in the electrolyte precursor as described above, thereby suppressing the increase in particle size and the expansion of particle size distribution, and improving the ionic conductivity of the obtained solid electrolyte.
[0163] From the same viewpoint, the solubility is more preferably 0.4 mass % or less, and further preferably 0.2 mass % or less. The lower limit of the solubility is not particularly limited, and is preferably 0 mass %, that is, completely insoluble, but is actually 0.01 mass % or more.
[0164] As the usage amount of the second solvent in contact, there is no particular restriction as long as the first solvent can be removed, for example, it can be set to be 50 mass parts or more and 10000 mass parts or less relative to 100 mass parts of electrolyte precursors. From the viewpoint of more efficiently and reliably removing the first solvent, it is preferably more than 100 mass parts, more preferably more than 300 mass parts, further preferably more than 500 mass parts, and as the upper limit, it is preferably less than 8000 mass parts, more preferably less than 5000 mass parts, and further preferably less than 3000 mass parts.
[0165] The contact between the electrolyte precursor and the second solvent may be performed at least once, preferably twice or more, from the viewpoint of more efficiently and reliably removing the first solvent, and the upper limit is preferably 8 times or less, more preferably 4 times or less.
[0166] As a method for contacting the electrolyte precursor with the second solvent, there is no particular limitation on the method as long as the two are in contact. For example, the method may be performed by a method generally referred to as solvent washing, i.e., mixing the electrolyte precursor and the second solvent and performing decantation or filtering using a glass filter to remove the second solvent.
[0167] The temperature conditions for contacting the electrolyte precursor with the second solvent are not particularly limited, and are, for example, -10 to 130° C., preferably 10 to 120° C., and more preferably room temperature (20° C.) to 110° C. Within the above temperature range, increase in particle size and increase in particle size distribution are easily suppressed.
[0168] Furthermore, from the viewpoint of reducing the particle size and reducing the particle size distribution in addition to suppressing the increase in particle size and the increase in particle size distribution, it is preferably 40 to 130°C, more preferably 60 to 120°C, further preferably 80 to 110°C, and further preferably 90 to 105°C.
[0169] [About contacts other than those mentioned above]
[0170] Next, "obtaining a solution containing an electrolyte precursor", "obtaining an electrolyte precursor", and "heating" other than "bringing the electrolyte precursor into contact with the second solvent" will be described in order.
[0171] As described above, in the manufacturing method of the present embodiment, if the electrolyte precursor is obtained by mixing the above-mentioned raw material content and the first solvent, no matter what kind of electrolyte precursor, as long as the electrolyte precursor is brought into contact with the second solvent, a sulfide solid electrolyte in which the increase in particle size and the expansion of particle size distribution are suppressed can be efficiently manufactured. The electrolyte precursor can be changed mainly according to the different raw materials contained in the raw material content, and is preferably divided into the following two modes (i) and (ii) according to the raw material content. Therefore, the raw material content is divided into the following cases for description.
[0172] Embodiment (i) includes the case of elemental sulfur;
[0173] Embodiment (ii) includes lithium sulfide, phosphorus sulfide, and at least one halogen atom-containing raw material selected from lithium halide and elemental halogen.
[0174] The raw materials contained in the raw material contents of embodiments (i) and (ii) are different, but the operations of "obtaining a solution containing an electrolyte precursor", "obtaining an electrolyte precursor", "contacting the electrolyte precursor with a second solvent" and "heating" are performed in any embodiment. However, due to the different raw materials, in the above-mentioned various operations, when "obtaining a solution containing an electrolyte precursor", "obtaining an electrolyte precursor" and "heating", the conditions are sometimes different. On the other hand, there are also cases where the conditions are the same. In addition, the raw material contents used in the manufacturing method of this embodiment are preferably the above-mentioned embodiments (i) and (ii), but are not limited to these embodiments.
[0175] The following description will be based on "obtaining a solution containing an electrolyte precursor", "obtaining an electrolyte precursor", and "heating" in embodiment (i). However, the contents of embodiment (ii) and parts corresponding to other embodiments are applicable to embodiment (ii) and other embodiments even if not specifically described.
[0176] [Implementation method (i)]
[0177] In the embodiment (i), the raw material content includes a plurality of raw materials containing at least one atom selected from lithium atoms, phosphorus atoms, sulfur atoms and halogen atoms, and includes elemental sulfur.
[0178] [Obtaining a solution containing an electrolyte precursor]
[0179] The manufacturing method of this embodiment prepares the electrolyte precursor before the electrolyte precursor contacts the second solvent, that is, comprises: mixing a raw material containing a plurality of raw materials in a first solvent to obtain a solution containing the electrolyte precursor, wherein the raw material contains at least one atom selected from lithium atoms, phosphorus atoms, sulfur atoms and halogen atoms.
[0180] The method of obtaining a solution containing an electrolyte precursor will first be described from the starting material content.
[0181] (Ingredients contained in raw materials)
[0182] The raw material content used in this embodiment is a content containing a plurality of raw materials containing at least one atom selected from lithium atoms, sulfur atoms, phosphorus atoms and halogen atoms, and in the case of embodiment (i), the raw material content contains elemental sulfur.
[0183] The atoms contained in the raw material are at least one atom selected from lithium atoms, sulfur atoms, phosphorus atoms and halogen atoms. From the viewpoint of improving ion conductivity, it is preferred to contain lithium atoms, sulfur atoms and phosphorus atoms, and it is more preferred to contain lithium atoms, sulfur atoms, phosphorus atoms and halogen atoms.
[0184] In the embodiment (i), as raw materials other than elemental sulfur contained in the raw material content, for example, representative examples include: lithium sulfide; lithium halides such as lithium fluoride, lithium chloride, lithium bromide, and lithium iodide; phosphorus sulfides such as phosphorus trisulfide (P2S3) and phosphorus pentasulfide (P2S5); various phosphorus fluorides (PF3, PF5), various phosphorus chlorides (PCl3, PCl5, P2Cl4), various phosphorus bromides (PBr3, PBr5), and various phosphorus iodides (PI3, P2I4); Thiophosphoryl halides such as thiophosphoryl fluoride (PSF3), thiophosphoryl chloride (PSCl3), thiophosphoryl bromide (PSBr3), thiophosphoryl iodide (PSI3), dichlorothiophosphoryl fluoride (PSCl2F), dibromothiophosphoryl fluoride (PSBr2F); and the like; raw materials composed of at least two atoms selected from the above four atoms, halogen elements such as fluorine (F2), chlorine (Cl2), bromine (Br2), iodine (I2), preferably chlorine (Cl2), bromine (Br2), iodine (I2).
[0185] Substances that can be used as raw materials other than the above-mentioned ones include, for example, raw materials containing at least one atom selected from the above-mentioned four atoms and atoms other than the four atoms. More specifically, they include: lithium compounds such as lithium oxide, lithium hydroxide, and lithium carbonate; alkali metal sulfides such as sodium sulfide, potassium sulfide, rubidium sulfide, and cesium sulfide; metal sulfides such as silicon sulfide, germanium sulfide, boron sulfide, gallium sulfide, tin sulfide (SnS, SnS2), aluminum sulfide, and zinc sulfide; phosphoric acid compounds such as sodium phosphate and lithium phosphate; halides of alkali metals other than lithium such as sodium iodide, sodium fluoride, sodium chloride, and sodium bromide; metal halides such as aluminum halides, silicon halides, germanium halides, arsenic halides, selenium halides, tin halides, antimony halides, tellurium halides, and bismuth halides; halogenated phosphorus oxides such as phosphorus oxychloride (POCl3) and phosphorus oxybromide (POBr3); and the like.
[0186] In the case of embodiment (i), the raw material content only needs to include elemental sulfur. If the ease of forming polysulfides is considered, lithium sulfide is preferably included among the above. In addition, phosphorus sulfides such as phosphorus trisulfide (P2S3) and phosphorus pentasulfide (P2S5) are preferred; halogen elements such as fluorine (F2), chlorine (Cl2), bromine (Br2), and iodine (I2); lithium halides such as lithium fluoride, lithium chloride, lithium bromide, and lithium iodide are preferred. In addition, when oxygen atoms are introduced into the solid electrolyte, lithium oxide, lithium hydroxide, and phosphoric acid compounds such as lithium phosphate are preferred.
[0187] The halogen atom is preferably a chlorine atom, a bromine atom, and an iodine atom, and at least one atom selected from these is preferred, and a combination of a chlorine atom and a bromine atom, or a bromine atom and an iodine atom is more preferred.
[0188] Therefore, as the above-mentioned lithium halide, preferably lithium chloride, lithium bromide, lithium iodide, more preferably the combination of lithium chloride and lithium bromide, lithium bromide and lithium iodide. As the halogen element, preferably chlorine (Cl2), bromine (Br2), iodine (I2), more preferably the combination of chlorine (Cl2) and bromine (Br2), bromine (Br2) and iodine (I2). In addition, lithium halide and halogen element can be used alone or in combination.
[0189] In the embodiment (i), as a combination of raw materials containing elemental sulfur, for example, a combination of lithium sulfide, elemental sulfur, phosphorus pentasulfide and lithium halide; a combination of lithium sulfide, elemental sulfur, phosphorus pentasulfide and a halogen element can be preferably exemplified. In addition, as the lithium halide, lithium chloride, lithium bromide and lithium iodide are preferred, and a combination of lithium chloride and lithium bromide, lithium bromide and lithium iodide is more preferred. As the halogen element, chlorine, bromine and iodine are preferred, and a combination of chlorine and bromine, bromine and iodine is more preferred.
[0190] Lithium sulfide, which is one of the above-mentioned preferred raw materials, can be produced by using lithium hydroxide and elemental sulfur in combination, for example. Therefore, when lithium sulfide is included as a raw material content, lithium sulfide can be commercially available lithium sulfide, or lithium sulfide obtained by reacting a raw material containing other lithium atoms such as lithium hydroxide with a raw material containing sulfur atoms such as elemental sulfur.
[0191] In this embodiment, Li3PS4 including a PS4 structure can also be used as a part of the raw material. Specifically, Li3PS4 and the like are prepared first and used as the raw material.
[0192] The content of Li3PS4 relative to the total of the raw materials is preferably 60 to 100 mol%, more preferably 65 to 90 mol%, and further preferably 70 to 80 mol%.
[0193] In addition, when Li3PS4 and a halogen element are used, the content of the halogen element relative to Li3PS4 is preferably 1 to 50 mol%, more preferably 10 to 40 mol%, further preferably 20 to 30 mol%, and further preferably 22 to 28 mol%.
[0194] The lithium sulfide used in this embodiment is preferably in the form of particles.
[0195] The average particle size of lithium sulfide particles (D 50 ) is preferably 0.1 μm to 1000 μm, more preferably 0.5 μm to 100 μm, and even more preferably 1 μm to 20 μm. In this specification, the average particle size (D 50) is the particle size when the particle size distribution cumulative curve is drawn from the smallest particle size to 50% (volume basis) of the whole, and the volume distribution is, for example, the average particle size that can be measured using a laser diffraction / scattering particle size distribution measuring device. In addition, among the raw materials exemplified as the above raw materials, the solid raw material preferably has an average particle size of the same degree as the above lithium sulfide particles, that is, the average particle size is preferably within the same range as the average particle size of the above lithium sulfide particles.
[0196] (About the blending ratio of raw materials)
[0197] In the embodiment (i), when elemental sulfur and lithium sulfide are used, the amount of elemental sulfur relative to lithium sulfide can be adopted without particular limitation. When elemental sulfur is used, as described above, the generation of sulfur radicals caused by the formation of lithium polysulfide through the reaction with lithium sulfide promotes the reaction with other raw materials, thereby obtaining a polysulfide as an electrolyte precursor.
[0198] The amount of elemental sulfur used relative to lithium sulfide varies depending on the type of sulfide solid electrolyte to be obtained by the production method of the present embodiment and cannot be generalized. However, when the sulfide solid electrolyte contains lithium atoms, phosphorus atoms, and sulfur atoms, it is preferably 0.5 mol or more, and more preferably 0.7 mol or more, relative to 1.0 mol of lithium sulfide.
[0199] When the sulfide solid electrolyte contains lithium atoms, phosphorus atoms, sulfur atoms and halogen atoms, it is preferably used in an excess amount exceeding 1.0 mole relative to 1.0 mole of lithium sulfide, and is more preferably 1.2 moles or more, more preferably 1.5 moles or more, and further preferably 1.7 moles or more. By using elemental sulfur in excess in this way, the generation of sulfur radicals is promoted, so that a sulfide solid electrolyte with improved ion conductivity can be efficiently produced.
[0200] In any of the above cases, the upper limit is not particularly limited, but from the viewpoint of obtaining a sulfide solid electrolyte more efficiently, it may be about 4.0 mol or less, and preferably 3.0 mol or less.
[0201] In addition, when the sulfide solid electrolyte to be obtained by the production method of the present embodiment contains lithium atoms, phosphorus atoms, sulfur atoms and halogen atoms, the amount of elemental sulfur used is preferably 110% or more, more preferably 130% or more, further preferably 150% or more, and further preferably 170% or more relative to the sulfur atoms required for the composition. The upper limit is not particularly limited, but from the viewpoint of more efficiently obtaining a sulfide solid electrolyte, it can be set to about 300% or less, preferably 280% or less, more preferably 250% or less, and further preferably 230% or less.
[0202] When lithium sulfide, elemental sulfur, phosphorus pentasulfide and lithium halide are used as raw materials, from the viewpoint of obtaining higher chemical stability and higher ion conductivity, the ratio of lithium sulfide to the total of lithium sulfide and phosphorus pentasulfide is preferably 65 to 85 mol%, more preferably 70 to 82 mol%, and even more preferably 74 to 80 mol%.
[0203] When lithium sulfide, elemental sulfur, phosphorus pentasulfide, lithium halide and other raw materials used as needed are used, the content of lithium sulfide and phosphorus pentasulfide relative to the total of these raw materials is preferably 50 to 99 mol%, more preferably 55 to 90 mol%, and even more preferably 60 to 85 mol%.
[0204] When lithium bromide and lithium iodide are used in combination as the lithium halide, from the viewpoint of improving ion conductivity, the ratio of lithium bromide to the total of lithium bromide and lithium iodide is preferably 1 to 99 mol%, more preferably 20 to 80 mol%, further preferably 35 to 80 mol%, and particularly preferably 45 to 70 mol%.
[0205] In addition, when lithium bromide and lithium chloride are used in combination as lithium halide, from the viewpoint of improving ion conductivity, the ratio of lithium bromide to the total of lithium bromide and lithium chloride is preferably 1 to 99 mol%, more preferably 15 to 75 mol%, further preferably 25 to 60 mol%, and particularly preferably 35 to 45 mol%.
[0206] When a halogen element is used as a raw material and lithium sulfide, elemental sulfur, and phosphorus pentasulfide are used, the ratio of the number of moles of lithium sulfide obtained by removing the same number of moles of lithium sulfide as the number of moles of the halogen element to the total number of moles of lithium sulfide and phosphorus pentasulfide obtained by removing the same number of moles of lithium sulfide as the number of moles of the halogen element is preferably in the range of 60 to 90%, more preferably in the range of 65 to 85%, further preferably in the range of 68 to 82%, further preferably in the range of 72 to 78%, and particularly preferably in the range of 73 to 77%. This is because these ratios can obtain higher ion conductivity.
[0207] Furthermore, from the same viewpoint, when lithium sulfide, elemental sulfur, phosphorus pentasulfide and a halogen element are used, the content of the halogen element relative to the total amount of lithium sulfide, phosphorus pentasulfide and the halogen element is preferably 1 to 50 mol %, more preferably 2 to 40 mol %, further preferably 3 to 25 mol %, and further preferably 3 to 15 mol %.
[0208] When lithium sulfide, elemental sulfur, phosphorus pentasulfide, a halogen element and a lithium halide are used, the content of the halogen element relative to the total amount of lithium sulfide, phosphorus pentasulfide, the halogen element and the lithium halide (α mol%) and the content of the lithium halide relative to the total amount of these (β mol%) preferably satisfy the following formula (2), more preferably satisfy the following formula (3), further preferably satisfy the following formula (4), and further preferably satisfy the following formula (5).
[0209] 2≤2α+β≤100…(2)
[0210] 4≤2α+β≤80…(3)
[0211] 6≤2α+β≤50…(4)
[0212] 6≤2α+β≤30…(5)
[0213] When two halogens are used as single substances, if the number of moles of one halogen atom in the substance is set to A1, and the number of moles of the other halogen atom in the substance is set to A2, then A1:A2 is preferably 1:99 to 99:1, more preferably 10:90 to 90:10, further preferably 20:80 to 80:20, and further preferably 30:70 to 70:30.
[0214] When two halogen elements are used and the two halogen elements are bromine and iodine, if the number of moles of bromine is set to A1 and the number of moles of iodine is set to A2, then A1:A2 is preferably 1:99 to 99:1, more preferably 20:80 to 80:20, further preferably 35:65 to 80:20, and further preferably 45:55 to 70:30.
[0215] Furthermore, when the two halogen elements are bromine and chlorine, if the number of moles of bromine is set to B1 and the number of moles of chlorine is set to B2, then B1:B2 is preferably 1:99 to 99:1, more preferably 15:85 to 75:25, further preferably 25:75 to 60:40, and further preferably 35:45 to 65:55.
[0216] When the blending ratio of the raw materials is set as above, it is easy to obtain the preferred crystal structure possessed by the sulfide solid electrolyte obtained by the production method of this embodiment, that is, the sulfide crystalline lithium superion conductor region II type crystal structure and the argyrodite type crystal structure.
[0217] (First solvent)
[0218] In the above embodiment (i), as the first solvent used when mixing the above raw materials, a solvent different from the second solvent may be used due to the relationship with the above second solvent. As the first solvent, a solvent other than the hydrocarbon solvent exemplified as the second solvent and adopted as the second solvent may be used, but it is preferred to use a solvent containing a heteroatom.
[0219] Preferred heteroatoms in the solvent include oxygen atoms, nitrogen atoms, sulfur atoms, chlorine atoms, phosphorus atoms, etc., and oxygen atoms and nitrogen atoms are preferred. The solvent containing heteroatoms may contain one or more of these heteroatoms.
[0220] As such a solvent containing heteroatoms, for example, there can be mentioned: solvents containing oxygen atoms such as alcohol solvents, ether solvents, ester solvents, aldehyde solvents, ketone solvents; solvents containing nitrogen atoms such as amine solvents and nitrile solvents; solvents containing oxygen atoms and nitrogen atoms such as amide solvents, etc. Among them, as solvents containing oxygen atoms, alcohol solvents and ether solvents are preferred, and as solvents containing nitrogen atoms, nitrile solvents are preferred. If these solvents are used, the generation of sulfur radicals and the formation of electrolyte precursors (polysulfides) are promoted, and a sulfide solid electrolyte with few impurities and high ionic conductivity can be efficiently obtained.
[0221] These solvents may be used alone or in combination. It is particularly preferred to use at least one organic solvent selected from alcohol solvents, ether solvents and nitrile solvents, and more preferably to use an alcohol solvent, an ether solvent and a nitrile solvent in combination. Since the generation of sulfur radicals and the formation of electrolyte precursors (polysulfides) are promoted in a well-balanced manner, a sulfide solid electrolyte with few impurities and high ion conductivity can be efficiently obtained.
[0222] (Alcohol solvent)
[0223] Examples of the alcohol solvent include aliphatic alcohols, alicyclic alcohols, heterocyclic alcohols and aromatic alcohols. In view of availability and cost, aliphatic alcohols, alicyclic alcohols and aromatic alcohols are preferred, and aliphatic alcohols are more preferred.
[0224] As the aliphatic alcohol, for example, representative and preferred examples include: saturated or unsaturated monovalent aliphatic alcohols such as methanol, ethanol, various propanols, allyl alcohol, various butanols, and various butenols; saturated or unsaturated polyvalent aliphatic alcohols such as various propylene glycols, various propylene glycols, various butanediols, various butene glycols, various hexanediols, various hexene glycols, various butanetriols, erythritol, pentaerythritol, and dipentaerythritol.
[0225] In this specification, for example, in the case of various butanols, "various" means that all conceivable isomers such as 1-butanol, 2-butanol, 2-methyl-1-propanol, and 1,1-dimethylethanol are included. In addition, even if "various" is not marked, compounds described in a form without specifying the substitution position number also include all conceivable isomers.
[0226] The aliphatic hydrocarbon group in the aliphatic alcohol may be linear or branched, and may be saturated or unsaturated.
[0227] The carbon number of the aliphatic alcohol is preferably 1 or more, more preferably 2 or more, and the upper limit is preferably 12 or less, more preferably 8 or less, and further preferably 4 or less.
[0228] The aliphatic alcohol may be a partially substituted aliphatic alcohol, and preferred examples include alkanolamines partially substituted with amino groups such as ethanolamine, propanolamine, and dimethylethanolamine; and alcohols partially substituted with halogen atoms such as fluoroalcohols.
[0229] Representative examples of the alicyclic alcohol include: monovalent or polyvalent saturated or unsaturated monocyclic alicyclic alcohols such as cyclopropanol, methylcyclopropanol, cyclopropanemethanol, cyclobutanol, cyclobutenol, cyclopentanol, cyclopentenol, cyclohexanol, methylcyclohexanol, cyclohexenol, cyclohexanediol, and cyclohexanetriol; and monovalent or polycyclic alicyclic alcohols such as cyclopentylcyclopentanol, cyclohexylcyclohexanol, cyclohexylphenylcyclohexanol, and dicyclohexanol.
[0230] The carbon number of the alicyclic alcohol is preferably 3 or more, and the upper limit is preferably 12 or less, more preferably 10 or less, and further preferably 8 or less.
[0231] The alicyclic alcohol may be partially substituted, and preferably, alicyclic alcohols partially substituted with saturated or unsaturated hydrocarbon groups (including linear and branched hydrocarbon groups) such as alkyl and alkenyl groups, for example, alicyclic alcohols partially substituted with amino groups such as aminomethylcyclopropanol, and alicyclic alcohols partially substituted with halogen atoms, etc. In addition, alicyclic alcohols substituted with substituents such as amide groups and cyano groups may be mentioned.
[0232] Representative examples of the heterocyclic alcohol include monocyclic alcohols such as oxetane alcohol, oxetane methanol, furfuryl alcohol, tetrahydrofurfuryl alcohol, tetrahydropyran methanol, morpholine alcohol, and pyridine methanol; and polycyclic condensed heterocyclic alcohols such as benzofuran methanol and dihydrobenzofuran methanol.
[0233] The number of carbon atoms in the heterocyclic alcohol is preferably 3 or more, and the upper limit is preferably 24 or less, more preferably 18 or less, and further preferably 12 or less.
[0234] The heterocyclic alcohol can be obtained by substituting a part of the alicyclic alcohol in the same manner as the above-mentioned alicyclic alcohol.
[0235] Representative and preferred examples of the aromatic alcohol include: monocyclic aromatic alcohols such as benzyl alcohol, salicyl alcohol, benzyl alcohol, methoxyphenyl alcohol, trimethoxyphenyl alcohol, and phenylethyl alcohol; polycyclic aromatic alcohols such as diphenyl alcohol and triphenyl alcohol; and condensed polycyclic aromatic alcohols such as naphthalene alcohol, anthracene alcohol, benzofuran alcohol, and dihydrobenzofuran alcohol.
[0236] The number of carbon atoms in the aromatic alcohol is preferably 7 or more, and the upper limit is preferably 24 or less, more preferably 20 or less, and further preferably 16 or less.
[0237] The aromatic alcohol can be obtained by partially substituting the alicyclic alcohol in the same manner as the above-mentioned alicyclic alcohol.
[0238] The above examples are merely representative examples of preferred alcohol solvents, and the solvents that can be used in the production method of the present embodiment are not limited to the above examples.
[0239] The alcohol solvent may be any of primary alcohol, secondary alcohol and tertiary alcohol, preferably primary alcohol. In addition, the alcohol solvent may be a monohydric alcohol having one hydroxyl group or a polyhydric alcohol having two or more hydroxyl groups, preferably a monohydric alcohol.
[0240] (Ether solvent)
[0241] Examples of the ether solvent include aliphatic ethers, alicyclic ethers, heterocyclic ethers and aromatic ethers. In view of availability and cost, aliphatic ethers, alicyclic ethers and aromatic ethers are preferred, aliphatic ethers and alicyclic ethers are more preferred, and alicyclic ethers are further preferred.
[0242] As the aliphatic ether, representative and preferred examples include: monoethers such as dimethyl ether, diethyl ether, diisopropyl ether, dibutyl ether, and tert-butyl methyl ether; diethers such as dimethoxymethane, dimethoxyethane, diethoxymethane, and diethoxyethane; polyethers having three or more ether groups such as diethylene glycol dimethyl ether (diglyme) and triethylene glycol dimethyl ether (triglyme); and ethers containing hydroxyl groups such as diethylene glycol and triethylene glycol.
[0243] The carbon number of the aliphatic ether is preferably 2 or more, more preferably 3 or more, and even more preferably 4 or more, and the upper limit is preferably 10 or less, more preferably 8 or less, and even more preferably 6 or less.
[0244] Furthermore, the aliphatic alcohol may be linear or branched.
[0245] Representative examples of the alicyclic ethers include monocyclic alicyclic ethers such as ethylene oxide, propylene oxide, furan, tetrahydrofuran, pyran, tetrahydropyran, dimethoxytetrahydrofuran, cyclopentyl methyl ether, dioxane, dioxene, dioxin, and dioxolane; and polycyclic alicyclic ethers such as dicyclopentyl ether and dicyclohexyl ether.
[0246] Typical examples of the heterocyclic ether include monocyclic heterocyclic ethers such as morpholine and hydroxymethyldimethoxypyridine; and polycyclic condensed heterocyclic ethers such as benzofuran, benzopyran, dibenzofuran and methoxyindole.
[0247] The carbon number of the alicyclic ether or heterocyclic ether is preferably 3 or more, and the upper limit is preferably 16 or less, more preferably 14 or less, and further preferably 10 or less.
[0248] In addition, typical and preferred examples of the aromatic ether include: monocyclic aromatic ethers such as methyl phenyl ether (anisole) and ethyl phenyl ether; polycyclic aromatic ethers such as dibenzyl ether, diphenyl ether and benzyl phenyl ether; and condensed polycyclic aromatic ethers such as benzylnaphthyl ether and bisnaphthyl ether.
[0249] The number of carbon atoms in the aromatic ether is preferably 7 or more, more preferably 8 or more, and the upper limit is preferably 16 or less, more preferably 14 or less, and further preferably 12 or less.
[0250] The ether compound used in this embodiment may be an ether compound substituted with a linear or branched hydrocarbon group such as an alkyl group or an alkenyl group, an alkoxy group (the alkyl group may be either linear or branched), a hydroxyl group, an amino group, an amide group, a cyano group or a halogen atom.
[0251] Among the above ether compounds, from the viewpoint of obtaining higher ion conductivity, alicyclic ethers are preferred, monocyclic alicyclic ethers are more preferred, and tetrahydrofuran is particularly preferred.
[0252] (Nitrile solvent)
[0253] Examples of the nitrile solvent include aliphatic nitrile, alicyclic nitrile, heterocyclic nitrile and aromatic nitrile. In view of availability and cost, aliphatic nitrile is preferred.
[0254] As the aliphatic nitriles, representative and preferred examples include: saturated or unsaturated aliphatic nitriles having one nitrile group, such as acetonitrile, acrylonitrile, methoxyacetonitrile, propionitrile, methoxypropionitrile, butyronitrile, etc.; saturated or unsaturated aliphatic nitriles having two or more nitrile groups, such as propane dinitrile, propane trinitrile, butane dinitrile, butene dinitrile, butane trinitrile, pentane dinitrile, pentane trinitrile, hexane dinitrile, hexene dinitrile, hexane trinitrile, methylene pentane dinitrile, etc.
[0255] The carbon number of the aliphatic nitrile is preferably 2 or more, and the upper limit is preferably 10 or less, more preferably 8 or less, and further preferably 4 or less. In addition, the carbon number of the aliphatic hydrocarbon group in the aliphatic nitrile is preferably 1 or more, and the upper limit is preferably 8 or less, more preferably 6 or less, and further preferably 2 or less.
[0256] Furthermore, the aliphatic hydrocarbon group in the aliphatic nitrile may be linear or branched.
[0257] As the alicyclic nitriles, representative and preferred examples include: monocyclic or polycyclic alicyclic nitriles having one nitrile group, such as cyanocyclopropane, cyclobutanecarbonitrile, hydroxycyclobutanecarbonitrile, oxocyclobutanecarbonitrile, cyclopentanecarbonitrile, furancarbonitrile, tetrahydropyrancarbonitrile, cyclohexanecarbonitrile, and bicyclobutanecarbonitrile; and alicyclic nitriles having two or more nitrile groups, such as furan dicarbonitrile, cyclobutane dicarbonitrile, cyclopentane dicarbonitrile, cyclohexane dicarbonitrile, and cyclohexane tricarbonitrile.
[0258] As heterocyclic nitriles, representative and preferred examples include: monocyclic heterocyclic nitriles having one or more nitrile groups such as morpholinecarbonitrile, tetrahydrofuranonitrile, cyanopyridine, pyridinedicarbonitrile, pyridinetricarbonitrile, furfurylmalononitrile, etc.; polycyclic or polycyclic condensed heterocyclic nitriles having one or more nitrile groups such as benzofurancarbonitrile, dibenzofurandicarbonitrile, dicyanobipyridine, etc.
[0259] The carbon number of the alicyclic nitrile or heterocyclic nitrile is preferably 3 or more, and the upper limit is preferably 16 or less, more preferably 14 or less, and further preferably 10 or less.
[0260] Representative examples of aromatic nitriles include monocyclic aromatic nitriles having one or more nitrile groups, such as benzyl cyanotoluene, benzonitrile, phthalonitrile, and benzene trimonitrile; and polycyclic or condensed polycyclic aromatic nitriles having one or more nitrile groups, such as biphenyl dicarbonitrile, phenylcyclobutane carbonitrile, naphthonitrile, naphthalenedicarbonitrile, naphthalene trimonitrile, anthracene carbonitrile, and cyclopentylbenzonitrile.
[0261] The number of carbon atoms in the aromatic nitrile is preferably 7 or more, more preferably 8 or more, and the upper limit is preferably 16 or less, more preferably 14 or less, and further preferably 12 or less.
[0262] The ether compound used in this embodiment may be an ether compound substituted with a linear or branched hydrocarbon group such as an alkyl group or an alkenyl group, an alkoxy group (the alkyl group may be either linear or branched), a hydroxyl group, an amino group, an amide group, a cyano group or a halogen atom.
[0263] (Other solvents with heteroatoms)
[0264] In addition, as the amine solvents exemplified as solvents having heteroatoms other than the above-mentioned alcohol solvents, ether solvents, and nitrile solvents, for example, preferably exemplified are: aliphatic amines such as ethylenediamine, diaminopropane, dimethylethylenediamine, tetramethylethylenediamine (TMEDA), and tetramethyldiaminopropane (TMPDA); alicyclic amines such as cyclopropylenediamine and cyclohexyldiamine; and heterocyclic aromatic amine solvents such as pyridine. In addition, as amide solvents, preferably exemplified are: amide solvents such as dimethylformamide, dimethylacetamide, hexamethylphosphoramide, and N-methylpyrrolidone; and the like.
[0265] (Other solvents)
[0266] When obtaining a solution containing an electrolyte precursor, when the above-mentioned solvent containing a heteroatom is used as the first solvent, as other solvents other than the above-mentioned first solvent, hydrocarbon solvents such as aliphatic hydrocarbon solvents, alicyclic hydrocarbon solvents, aromatic hydrocarbon solvents, etc. exemplified as the above-mentioned second solvent may be used.
[0267] In this case, as the usage amount of other solvents, its usage amount is less and more preferred, for example, relative to the usage amount of 100.0 parts by volume of the above-mentioned first solvent, it is preferably below 50.0 parts by volume, more preferably below 30.0 parts by volume, and further preferably below 15.0 parts by volume. In addition, it is of course preferred not to use other solvents and only use the above-mentioned first solvent.
[0268] (Amount of the first solvent used)
[0269] In the production method of the present embodiment, when an alcohol solvent is used as the first solvent, the amount of the alcohol solvent used is preferably 0.005 mol or more, more preferably 0.010 mol or more, further preferably 0.015 mol or more, further preferably 0.020 mol or more, relative to 1.0 mol of lithium sulfide used as a raw material, and the upper limit is preferably 20.0 mol or less, more preferably 16.0 mol or less, further preferably 10.0 mol or less.
[0270] In addition, when using at least one organic solvent selected from an alcohol solvent, an ether solvent and a nitrile solvent and using an alcohol solvent, the total amount of the ether solvent and the nitrile solvent used is preferably 2.0 parts by volume or more, more preferably 5.0 parts by volume or more, further preferably 15.0 parts by volume or more, further preferably 50.0 parts by volume or more, and particularly preferably 150.0 parts by volume or more, and the upper limit is preferably 10000.0 parts by volume or less, more preferably 9000.0 parts by volume or less, further preferably 8000.0 parts by volume or less, and further preferably 1.0 parts by volume or less.
[0271] (mix)
[0272] The manufacturing method of this embodiment mixes the raw material containing material in the above-mentioned first solvent. By mixing the raw material containing material in the first solvent, a solution containing an electrolyte precursor is obtained. In embodiment (i), the electrolyte precursor (polysulfide) is generated via sulfur radicals, so a sulfide solid electrolyte with less impurities and high ion conductivity can be efficiently obtained.
[0273] There is no particular limitation on the method of mixing the raw material content in the first solvent, as long as the first solvent and the raw material content are put into a device capable of mixing the raw material content in the first solvent and mixed. For example, it is preferred to supply the first solvent to the tank, operate the stirring blade, and then gradually add the raw material content. In addition, it is also preferred to supply the raw material content to the tank, operate the stirring blade, and then gradually add the first solvent. Since a good mixing state of the raw material content can be obtained, the dispersibility of the raw material is improved, and the generation of sulfur radicals and the formation of electrolyte precursors (polysulfides) are promoted.
[0274] However, when a halogen element is used as a raw material, the raw material is sometimes not solid. Specifically, at normal temperature and pressure, fluorine and chlorine become gases, and bromine becomes liquid. In such a case, for example, when the raw material is liquid, it can be supplied to the tank together with the solvent separately from other solid raw materials. In addition, when the raw material is gas, it can be supplied in a manner of blowing into a substance obtained by adding a solid raw material to a solvent.
[0275] The order in which the raw materials containing the raw materials are added and mixed is not particularly limited, but in consideration of work efficiency, all the raw materials are preferably added at the same time and mixed at once.
[0276] In addition, if considering improving the solubility of the raw materials, further suppressing the generation of impurities, and more efficiently obtaining a sulfide solid electrolyte with high ion conductivity, it is preferred to divide the raw materials into two raw material groups, raw material group 1 and raw material group 2, and mix them in batches by mixing raw material group 1 and then raw material group 2.
[0277] In the case of batch mixing, the raw material group 1 preferably contains elemental sulfur. This promotes the formation of sulfur radicals and more efficiently obtains a sulfide solid electrolyte having high ion conductivity.
[0278] From the same viewpoint, the combination of raw material group 1 and raw material group 2 is preferred, wherein raw material group 1 includes a raw material including at least one atom selected from lithium atoms, phosphorus atoms and sulfur atoms, elemental sulfur and lithium sulfide, and raw material group 2 includes a raw material including a halogen atom. This is because the raw material group 1 includes elemental sulfur and lithium sulfide, and the reaction of these elements promotes the formation of sulfur radicals through lithium polysulfide. In addition, from the same viewpoint, the combination of raw material group 1 and raw material group 2 is also preferred, wherein raw material group 1 includes a raw material including a halogen atom, elemental sulfur and lithium sulfide, and raw material group 2 includes a raw material including a phosphorus atom and a sulfur atom.
[0279] In the production method of the present embodiment, the order of charging and mixing the raw materials may be selected according to whether priority is given to work efficiency or to the ion conductivity of the sulfide solid electrolyte.
[0280] In addition, as described above, in the manufacturing method of the present embodiment, as a raw material included in the raw material content, Li3PS4 or the like containing a PS4 structure can be prepared and used. Li3PS4 can be manufactured by, for example, mixing lithium sulfide and phosphorus pentasulfide at a molar ratio of 75:25, respectively. In the manufacturing method of the present embodiment, when phosphorus pentasulfide is used as a raw material in addition to lithium sulfide, a raw material group containing lithium sulfide and phosphorus pentasulfide and elemental sulfur at a specified molar ratio of 75:25 or the like can be mixed in a solvent as raw material group 1, and then a raw material containing halogen atoms such as lithium halide, other remaining raw materials required for manufacturing the desired sulfide solid electrolyte, such as a raw material group containing the insufficient part of lithium sulfide, is added as raw material group 2 and mixed. By pre-forming an electrolyte precursor (polysulfide) containing the basic structure of Li3PS4, a sulfide solid electrolyte can be obtained more efficiently.
[0281] Here, the predetermined molar ratio of the lithium sulfide to the phosphorus pentasulfide is preferably 55 to 85:15 to 45, more preferably 60 to 80:20 to 40, and even more preferably 65 to 75:25 to 35.
[0282] The manufacturing method of the present embodiment is characterized in that it includes: mixing the raw material content in the first solvent. That is, the raw material content only needs to be mixed, and there is no need to pulverize it. Therefore, it is possible to manufacture it by a method that does not use a device generally called a pulverizer used for the purpose of pulverizing the raw material, such as a media pulverizer such as a ball mill or a bead mill. In the manufacturing method of the present embodiment, the solvent and the raw material are mixed only by simply mixing the raw material content in the solvent, and a polysulfide as an electrolyte precursor is generated. By decomposing it by heating or the like, an amorphous sulfide solid electrolyte can be formed, and then a crystalline sulfide solid electrolyte can be formed.
[0283] In order to shorten the mixing time for obtaining the electrolyte precursor or to pulverize the mixture of the raw materials in the solvent, a pulverizer may be used. However, as described above, it is preferred not to use a pulverizer.
[0284] As a device for mixing the raw material content in the first solvent, for example, a mechanical stirring mixer with stirring blades in a tank can be cited. The mechanical stirring mixer can be exemplified by a high-speed stirring mixer, a double-arm mixer, etc., and from the viewpoint of improving the uniformity of the raw materials in the mixture of the raw material content and obtaining higher ion conductivity, a high-speed stirring mixer is preferably used. In addition, as a high-speed stirring mixer, a vertical axis rotating mixer, a horizontal axis rotating mixer, etc. can be cited, and any type of mixer can also be used.
[0285] As the shape of the stirring blade used in the mechanical stirring mixer, anchor type, blade type, arm type, belt type, multi-stage blade type, two-arm type, bucket type, biaxial blade type, flat blade type, C-type blade type etc. can be exemplified. From the viewpoint of improving the uniformity of raw materials and obtaining higher ionic conductivity, bucket type, flat blade type, C-type blade type are preferably used. In addition, in the mechanical stirring mixer, a circulation line that returns to the inside of the mixer again after the stirring object is discharged to the outside of the mixer is preferably set. Thus, raw materials with heavier specific gravity such as lithium halides will not precipitate and will not be stirred by retention, and more uniform mixing can be carried out.
[0286] Although the location of the circulation line is not particularly limited, it is preferably located at a location where the liquid is discharged from the bottom of the mixer and returned to the upper part of the mixer. Thus, it is easy for the raw materials that are easy to precipitate to be uniformly stirred along with the convection of the circulation. Furthermore, it is preferred that the return port is located below the liquid surface of the stirring object. Thus, it is possible to suppress the splashing of the liquid and make the stirring object adhere to the wall surface inside the mixer.
[0287] There is no particular upper limit to the mixing time when mixing the raw material-containing material in the first solvent. Taking efficiency into consideration, it is preferably 240 minutes or less, more preferably 60 minutes or less, further preferably 30 minutes or less, and further preferably 15 minutes or less. The lower limit is usually 0.1 minutes or more, preferably 1 minute or more, and further preferably 3 minutes or more.
[0288] The temperature conditions for mixing the raw material content in the solvent are not particularly limited, but are, for example, -30 to 100°C, preferably -10 to 50°C, and more preferably around room temperature (20°C) (eg, around room temperature ±5°C).
[0289] [Obtaining electrolyte precursor]
[0290] The manufacturing method of this embodiment includes: removing the first solvent from the solution obtained by the above-mentioned operation of obtaining a solution containing an electrolyte precursor to obtain an electrolyte precursor. In the manufacturing method of this embodiment, since a solution containing an electrolyte precursor is obtained, it is necessary to remove the solvent from the solution to obtain a powder of the electrolyte precursor. This is because the electrolyte precursor dissolved in the solution cannot contact the second solvent.
[0291] The method of removing the solvent from the solution containing the electrolyte precursor is not particularly limited, and for example, a method using drying may be mentioned.
[0292] As drying conditions, the drying temperature varies depending on the pressure conditions for drying, the boiling point of the first solvent, etc., and therefore cannot be generalized, but is usually 5° C. or higher and lower than 200° C., preferably 20° C. to 190° C., more preferably 35 to 175° C., and further preferably 50 to 160° C. In addition, as pressure conditions, the drying can be carried out under normal pressure or under pressure, but it is preferably carried out under reduced pressure drying (vacuum drying) using a vacuum pump or the like.
[0293] The drying time is usually 1 minute to 10 hours, preferably 10 minutes to 8 hours, more preferably 30 minutes to 6 hours, and further preferably 1 hour to 5 hours.
[0294] In this way, a powder of the electrolyte precursor dissolved in the solution containing the electrolyte precursor is obtained by drying or the like. By obtaining the electrolyte precursor as the powder of the electrolyte precursor, the electrolyte precursor can be brought into contact with the second solvent.
[0295] In embodiment (i), obtaining the electrolyte precursor can be performed by the same operation as the "first heating" in the "heating" described later, or can be performed by "first heating-1" and "first heating-2". The heating temperature in the "first heating" is above 20°C and below 150°C as described later, and is substantially within the range of the drying temperature in the above-mentioned "method using drying". Therefore, if the temperature condition of the "first heating" described later is used, even if the above-mentioned drying temperature condition is considered, it is difficult to produce granulation caused by the residual solvent and heating. In addition, the same operation as the above-mentioned "first heating" when obtaining the electrolyte precursor can be performed on a solution containing the electrolyte precursor, that is, on a solution containing the electrolyte precursor and the first solvent, and there is no need to replace the first solvent with the second solvent.
[0296] The operation of obtaining the electrolyte precursor is performed by the same operation as the "first heating" described later. After the electrolyte precursor is contacted with the second solvent, during heating, it can be heated by the methods of "first heating" and "second heating", or the "first heating" can be omitted and the "second heating" can be performed. Here, in the case of performing the "first heating", it can also be divided into "first heating-1" and "first heating-2" to perform. In short, the operation of obtaining the electrolyte precursor is performed by the same operation as the "first heating". As described above, granulation is not easy to occur, so the particle size and particle size distribution can be further reduced, and the increase of the particle size and the change of the particle size distribution can be further suppressed.
[0297] The details of obtaining the electrolyte precursor in embodiment (ii) will be described later, but the electrolyte precursor can be obtained by the same operation as the "first heating" in the "heating" in embodiment (i), or can be divided into "first heating-1" and "first heating-2".
[0298] 〔Heating〕
[0299] The production method of the present embodiment includes removing the solvent from the solution containing the electrolyte precursor to prepare the electrolyte precursor, bringing the electrolyte precursor into contact with a second solvent, and then heating.
[0300] The heating temperature is not particularly limited as long as it is room temperature or higher, and the room temperature may vary, so it cannot be generalized, but it is usually preferably 20° C. or higher, and the upper limit is preferably 500° C. or lower. When the heating temperature is within the above range, decomposition of polysulfides, removal of solvents, and removal of elemental sulfur can be performed more efficiently, and crystallization can be performed.
[0301] In the embodiment (i), the formation of a sulfide solid electrolyte caused by the decomposition of the generated polysulfide (i.e., electrolyte precursor), the removal of elemental sulfur generated by the decomposition of the polysulfide, the removal of the solvent and crystallization can be performed by heating. The heating temperature in the embodiment (i) is preferably set within the above-mentioned heating temperature range, i.e., 20° C. to 500° C.
[0302] In the embodiment (i), the heating is preferably performed in multiple stages. For example, it is preferred to perform heating (first heating) mainly for decomposing the generated polysulfide, removing the solvent and removing the elemental sulfur, and then perform heating (second heating) for crystallization. More specifically, it is preferred to perform the first heating at a heating temperature of 20° C. or higher and lower than 150° C. and the second heating at a heating temperature of 150° C. or higher and 500° C. or lower.
[0303] The heating temperature in the first heating may be 20° C. or higher and lower than 150° C. For example, the first heating may be performed by heating at a lower temperature and then heating at a higher temperature, that is, by performing heating in multiple stages.
[0304] Generally, the removal of the solvent starts at 20°C or higher, the decomposition of the polysulfide starts at 60°C or higher, and the removal of sulfur starts at 100°C or higher. By performing multi-stage heating at heating temperatures corresponding to these purposes, each purpose can be more efficiently achieved, so it is easy to obtain a sulfide solid electrolyte with improved ion conductivity. In particular, with respect to the removal of elemental sulfur, by reliably performing this removal, the generation of impurities caused by the residual elemental sulfur can be further suppressed, so it is easy to obtain a sulfide solid electrolyte with improved ion conductivity.
[0305] For example, the heating temperature when heating at a lower temperature (first heating-1) is preferably 20° C. or higher, and the upper limit is preferably lower than 60° C., more preferably 50° C. or lower. By setting the temperature in such a range, the solvent can be removed.
[0306] Next, the heating temperature when heating at a higher temperature (first heating-2) is preferably 60° C. or higher, more preferably 65° C. or higher, further preferably 75° C. or higher, further preferably 95° C. or higher, and particularly preferably 110° C. or higher, and the upper limit is lower than 150° C., more preferably 145° C. or lower, further preferably 135° C. or lower, and further preferably 130° C. or lower. By setting the temperature in such a range, decomposition of polysulfides and removal of sulfur can be mainly performed.
[0307] As described above, the first heating can remove the solvent, decompose the polysulfide, and remove the sulfur depending on the heating temperature, so various methods can be adopted by adjusting the heating temperature. For example, if the heating temperature of the first heating is set to 60°C or higher (lower than 100°C), the solvent can be removed and the polysulfide can be decomposed, so it is set as the first heating-1, and the sulfur can be removed by heating at 100°C or higher (lower than 150°C) as the first heating-2. In this case, the first heating-2 can be omitted, and the sulfur can be removed by a method other than heating, that is, solvent washing, hydrodesulfurization, etc., and then the second heating can be performed. In addition, the method of solvent washing, hydrodesulfurization, etc. for removing sulfur will be described later.
[0308] In addition, for example, the following three-stage heating can be performed: if the heating temperature of the first heating is set to 20°C or higher (lower than 60°C), the solvent can be removed, so it is set as the first heating-1, if it is heated at 60°C or higher (lower than 100°C) as the first heating-2, polysulfide can be decomposed, and further, it is heated at 100°C or higher (lower than 150°C) as the first heating-3 to remove sulfur. In this case, it is also possible to remove sulfur by a method other than heating as described above instead of the first heating-3, and by setting the heating temperature of the first heating-2 to 100°C or higher (lower than 150°C), it is also possible to decompose polysulfide and remove sulfur at the same time.
[0309] In the above, the case where the first heating is performed by multi-stage heating is described. However, if the heating temperature of the first heating is set to 100° C. or higher, for example, the solvent can be removed, polysulfide can be decomposed, and sulfur can be removed. Therefore, multi-stage heating may not be performed.
[0310] The heating time of the first heating is not particularly limited as long as it is the time of the degree that can remove the solvent at least, for example, is preferably more than 10 minutes, more preferably more than 30 minutes, more preferably more than 45 minutes, and more preferably more than 1 hour. In addition, the upper limit of the heating time is not particularly limited, and is preferably less than 24 hours, more preferably less than 10 hours, more preferably less than 5 hours, and more preferably less than 3 hours.
[0311] The pressure condition during the first heating is preferably set to normal pressure or reduced pressure. When set to reduced pressure, specifically, it is preferably below 85 kPa, more preferably below 80 kPa, and further preferably below 70 kPa. The lower limit may be vacuum (0 kPa). Considering the ease of adjusting the pressure, it is preferably above 1 kPa, more preferably above 2 kPa, and further preferably above 3 kPa.
[0312] In addition, the heating is preferably performed in an inert gas atmosphere (e.g., a nitrogen atmosphere, an argon atmosphere) or in a reduced pressure atmosphere (particularly in a vacuum). For example, an inert gas atmosphere containing a certain concentration of hydrogen may also be used. This is because the degradation (e.g., oxidation) of the sulfide solid electrolyte can be prevented.
[0313] As described above, "obtaining an electrolyte precursor" can be performed by the same operation as the above-mentioned "first heating". In this case, the "first heating" can be omitted or performed. If it is considered that each purpose can be more efficiently achieved by performing multi-stage heating at a heating temperature corresponding to the purpose, it is preferred to perform the "first heating".
[0314] The heating temperature in the second heating cannot be generalized because it can be changed depending on the sulfide solid electrolyte to be produced. However, considering the relationship with the first heating, it can be 150°C to 500°C, preferably 160°C or more, more preferably 200°C or more, and further preferably 240°C or more. The upper limit is preferably 480°C or less, more preferably 460°C or less, and further preferably 440°C or less.
[0315] The second heating may be performed in multiple stages as in the first heating. By performing multiple stages of heating as the second heating, more reliable crystallization can be achieved.
[0316] In the case of multi-stage heating, for example, the heating temperature when heating at a lower heating temperature (second heating-1) is set to 150°C or more and less than 270°C, and the heating temperature when heating at a higher heating temperature (second heating-2) is set to 270°C or more and 500°C or less. As the lower limit of the second heating-1, it is preferably set to the temperature of the lower limit of the second heating, and as the upper limit, it is preferably 265°C or less, and more preferably 255°C or less. In addition, as the upper limit of the second heating-2, it is preferably set to the temperature of the upper limit of the second heating, and as the lower limit, it is preferably 290°C or more, more preferably 340°C or more, and further preferably 375°C or more.
[0317] The heating time and pressure conditions in the second heating are the same as those in the first heating, and the heating time and pressure conditions are also the same in that the second heating is preferably performed in an inert gas atmosphere.
[0318] The heating method is not particularly limited, and examples thereof include methods using various heating devices such as a hot plate, a vacuum heating device, an argon atmosphere furnace, a firing furnace, and a vacuum firing furnace. In addition, in industry, a horizontal dryer or a horizontal vibrating fluidized dryer having a heating unit and a feeding mechanism can also be used, and the method can be selected according to the amount of heating treatment.
[0319] (Sulfur Removal)
[0320] In embodiment (i), elemental sulfur is used as a raw material, and the electrolyte precursor is a polysulfide. Therefore, as described above, sulfur can be removed by heating, but sometimes residual sulfur remains. In this case, sulfur removal can also be performed by methods other than heating. For example, when the temperature of the first heating is set to be lower than 100° C., sulfur removal is preferably performed by methods other than heating. As a method for removing sulfur, for example, solvent removal, hydrodesulfurization, and the like can be cited.
[0321] The method of washing with a solvent includes, for example, washing the first heated powder with a solvent that dissolves sulfur, such as an aromatic hydrocarbon solvent such as benzene, toluene, or xylene; or a sulfur-containing organic solvent such as carbon disulfide, to remove sulfur.
[0322] In addition, the contact of the electrolyte precursor with the second solvent in the manufacturing method of the present embodiment can also be said to be a scheme of solvent cleaning. Therefore, by contacting before heating, in addition to the removal of the solvent attached to the electrolyte precursor, sulfur removal may also occur. Therefore, sulfur removal may not be performed separately. In addition, for example, in the case where the temperature of the first heating is set to be lower than 100° C. as described above, sulfur removal may also be performed in the case where the solvent removal is desired to be performed more reliably.
[0323] As a method of removing sulfur by solvent washing, for example, the first heated powder is washed with a solvent that dissolves sulfur, such as an aromatic hydrocarbon solvent such as benzene, toluene, or xylene; or a sulfur-containing organic solvent such as carbon disulfide, to remove sulfur.
[0324] As a method utilizing hydrodesulfurization, the powder subjected to the first heating is mixed with a hydrodesulfurization catalyst, and hydrogen is passed through the mixture while heating at 300 to 450° C., thereby removing sulfur by a hydrodesulfurization reaction. Here, as the hydrodesulfurization catalyst, preferably, a porous catalyst containing nickel, molybdenum, cobalt, tungsten, or the like as an active metal element, such as a NiMo catalyst, a CoMo catalyst, or a NiW catalyst, can be cited.
[0325] (Amorphous sulfide solid electrolyte)
[0326] In the embodiment (i) of the production method of the present embodiment, an amorphous sulfide solid electrolyte is produced by performing the above-mentioned first heating mainly for removing the solvent.
[0327] The amorphous sulfide solid electrolyte generated in the manufacturing method of this embodiment contains lithium atoms, sulfur atoms, phosphorus atoms and halogen atoms. As representative amorphous sulfide solid electrolytes, for example, solid electrolytes composed of lithium sulfide, phosphorus sulfide and lithium halide, such as Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, Li2S-P2S5-LiI-LiBr, etc., can be preferably cited; solid electrolytes containing other atoms such as oxygen atoms and silicon atoms, such as Li2S-P2S5-Li2O-LiI, Li2S-SiS2-P2S5-LiI, etc. From the viewpoint of obtaining higher ionic conductivity, solid electrolytes composed of lithium sulfide, phosphorus sulfide and lithium halide, such as Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, Li2S-P2S5-LiI-LiBr, etc. are preferred.
[0328] The types of atoms constituting the sulfide solid electrolyte can be confirmed by, for example, an ICP emission spectrometer.
[0329] In the sulfide solid electrolyte (amorphous sulfide solid electrolyte and crystalline sulfide solid electrolyte) obtained by the production method of the present embodiment, the composition ratio (molar ratio) of lithium atoms, phosphorus atoms, sulfur atoms and halogen atoms is preferably 1.0 to 1.8: 0.1 to 0.8: 1.0 to 2.0: 0.01 to 0.6, more preferably 1.1 to 1.7: 0.2 to 0.6: 1.2 to 1.8: 0.05 to 0.5, and further preferably 1.2 to 1.6: 0.25 to 0.5: 1.3 to 1.7: 0.08 to 0.4. In addition, when bromine and iodine, or bromine and chlorine are used in combination as halogen atoms, the composition ratio (molar ratio) of lithium atoms, phosphorus atoms, sulfur atoms, bromine, and iodine (or chlorine) is preferably 1.0-1.8: 0.1-0.8: 1.0-2.0: 0.01-0.3: 0.01-0.3, more preferably 1.1-1.7: 0.2-0.6: 1.2-1.8: 0.02-0.25: 0.02-0.25, further preferably 1.2-1.6: 0.25-0.5: 1.3-1.7: 0.03-0.2: 0.03-0.2, and further preferably 1.35-1.45: 0.3-0.45: 1.4-1.7: 0.04-0.18: 0.04-0.18.
[0330] By setting the composition ratio (molar ratio) of lithium atoms, sulfur atoms, phosphorus atoms and halogen atoms within the above-mentioned range, a solid electrolyte with higher ionic conductivity having a sulfide crystalline lithium superion conductor region type II crystal structure or an argyrodite-type crystal structure in the crystal structure described later can be easily obtained.
[0331] The shape of the amorphous sulfide solid electrolyte is not particularly limited, and may be, for example, a particle shape.
[0332] The average particle size (D 50 ), for example, 0.01 μm or more, further 0.03 μm or more, 0.05 μm or more, 0.1 μm or more, and the upper limit is 200.0 μm or less, further 100.0 μm or less, 90.0 μm or less, 80.0 μm or less, 70.0 μm or less.
[0333] (Crystalline sulfide solid electrolyte)
[0334] The crystalline sulfide solid electrolyte obtained by the manufacturing method of this embodiment can be a so-called glass ceramic obtained by heating an amorphous sulfide solid electrolyte to a crystallization temperature or higher. As its crystal structure, preferably, Li3PS4 crystal structure, Li4P2S6 crystal structure, Li7PS6 crystal structure, Li7P3S 11 A crystal structure, a crystal structure having peaks near 2θ=20.2° and 23.6° (for example, Japanese Patent Application Laid-Open No. 2013-16423), and the like.
[0335] Li can also be preferably exemplified 4-x Ge 1-x P x The S4 type sulfide crystalline lithium superion conductor region II (thio-LISICONRegion II) type crystal structure (see Kanno et al., Journal of The Electrochemical Society, 148 (7) A742-746 (2001)), and Li 4-x Ge 1-x P x The crystal structure similar to the S4 type sulfide crystalline lithium superion conductor region II (thio-LISICON Region II) type (see Solid State Ionics, 177 (2006), 2721-2725) etc.
[0336] From the perspective of obtaining higher ion conductivity, the crystal structure of the crystalline sulfide solid electrolyte obtained by the manufacturing method of this embodiment is preferably a sulfide crystalline lithium superion conductor region type II crystal structure among the above. Here, "sulfide crystalline lithium superion conductor region type II crystal structure" means Li 4-x Ge 1-x P xS4-type sulfide crystalline lithium superion conductor region II (thio-LISICON Region II) crystal structure, and Li 4-x Ge 1-x P x Any crystal structure similar to the S4 type thio-LISICON Region II type.
[0337] The crystalline sulfide solid electrolyte obtained by the manufacturing method of this embodiment may be a crystalline sulfide solid electrolyte containing the above-mentioned sulfide crystallized lithium superion conductor region type II crystal structure, or may be a crystalline sulfide solid electrolyte containing the sulfide crystallized lithium superion conductor region type II crystal structure as a main crystal. From the viewpoint of obtaining higher ionic conductivity, it is preferred that the sulfide crystallized lithium superion conductor region type II crystal structure be contained as a main crystal. In this specification, "containing as a main crystal" means that the proportion of the target crystal structure in the crystal structure is 80% or more, preferably 90% or more, and more preferably 95% or more. In addition, from the viewpoint of obtaining higher ionic conductivity, the crystalline sulfide solid electrolyte obtained by the manufacturing method of this embodiment preferably does not contain crystalline Li3PS4 (β-Li3PS4).
[0338] In the X-ray diffraction measurement using CuKα rays, the diffraction peaks of the Li3PS4 crystal structure appear, for example, at 2θ=17.5°, 18.3°, 26.1°, 27.3°, and 30.0°; the diffraction peaks of the Li4P2S6 crystal structure appear, for example, at 2θ=16.9°, 27.1°, and 32.5°; the diffraction peaks of the Li7PS6 crystal structure appear, for example, at 2θ=15.3°, 25.2°, 29.6°, and 31.0°; and the diffraction peaks of the Li7P3S 11 The diffraction peaks of the crystal structure appear near 2θ=17.8°, 18.5°, 19.7°, 21.8°, 23.7°, 25.9°, 29.6°, and 30.0°, for example. 4-x Ge 1-x P x The diffraction peaks of the S4-type sulfide crystalline lithium superion conductor region II (thio-LISICON Region II) crystal structure appear near 2θ=20.1°, 23.9°, and 29.5°, which are similar to Li 4-x Ge 1-x P x The diffraction peaks of the S4 type thio-LISICON Region II-type crystal structure appear near 2θ=20.2° and 23.6°, for example. These peak positions may fluctuate within a range of ±0.5°.
[0339] Crystalline sulfide solid electrolytes having the following crystal structures can also be preferably exemplified: having the structural framework of Li7PS6 as described above, and a thiogermanate-type crystal structure in which a part of P is replaced by Si.
[0340] As a compositional formula of the thiogermanate-type crystal structure, for example, a compositional formula of Li 7-x P 1-y Si y S6 and Li 7+x P 1- y Si y S6 (where x is -0.6 to 0.6 and y is 0.1 to 0.6) can be exemplified. The thiogermanate-type crystal structure represented by this compositional formula is cubic or orthorhombic, preferably cubic, and in X-ray diffraction measurement using CuKα rays, mainly has peaks appearing at positions of 2θ = 15.5°, 18.0°, 25.0°, 30.0°, 31.4°, 45.3°, 47.0°, and 52.0°.
[0341] As a compositional formula of the thiogermanate-type crystal structure, a compositional formula of Li 7-x-2y PS 6-x-y Cl x (0.8 ≤ x ≤ 1.7, 0 < y ≤ -0.25x + 0.5) can also be exemplified. The thiogermanate-type crystal structure represented by this compositional formula is preferably cubic, and in X-ray diffraction measurement using CuKα rays, mainly has peaks appearing at positions of 2θ = 15.5°, 18.0°, 25.0°, 30.0°, 31.4°, 45.3°, 47.0°, and 52.0°.
[0342] In addition, as a compositional formula of the thiogermanate-type crystal structure, a compositional formula of Li 7-x PS 6-x Ha x (where Ha is Cl or Br, and x is preferably 0.2 to 1.8) can also be exemplified. The thiogermanate-type crystal structure represented by this compositional formula is preferably cubic, and in X-ray diffraction measurement using CuKα rays, mainly has peaks appearing at positions of 2θ = 15.5°, 18.0°, 25.0°, 30.0°, 31.4°, 45.3°, 47.0°, and 52.0°.
[0343] In addition, these peak positions can fluctuate within a range of ±0.5°.
[0344] As the crystalline sulfide solid electrolyte obtained by the production method of the present embodiment, among the above, a crystalline sulfide solid electrolyte having a sulfide crystalline lithium superion conductor region II type crystal structure and a crystalline sulfide solid electrolyte having an argyrodite type crystal structure are preferred.
[0345] The shape of the crystalline sulfide solid electrolyte is not particularly limited, and may be, for example, a particle shape.
[0346] The average particle size (D 50 ), for example, 0.01 μm or more, further 0.03 μm or more, 0.05 μm or more, 0.1 μm or more, and the upper limit is 200.0 μm or less, further 100.0 μm or less, 90.0 μm or less, 80.0 μm or less, 70.0 μm or less.
[0347] [Implementation method (ii)]
[0348] In the case of implementation mode (ii), the raw material contains a plurality of raw materials containing at least one atom selected from lithium atoms, phosphorus atoms, sulfur atoms and halogen atoms, and contains lithium sulfide, phosphorus sulfide and at least one halogen atom-containing raw material selected from lithium halides and elemental halogens.
[0349] [Obtaining a solution containing an electrolyte precursor]
[0350] The method of obtaining a solution containing an electrolyte precursor in the embodiment (ii) will be described from the perspective of the raw material contents.
[0351] (Ingredients contained in raw materials)
[0352] The raw material content used in embodiment (ii) includes a plurality of raw materials containing at least one atom selected from lithium atoms, phosphorus atoms, sulfur atoms and halogen atoms, and includes lithium sulfide, phosphorus sulfide and at least one halogen atom-containing raw material selected from lithium halides and elemental halogens. In addition, the raw material content used in embodiment (ii) preferably does not contain elemental sulfur. Thus, the raw materials used in embodiments (i) and (ii) are different.
[0353] The raw material content used in embodiment (ii) is different from the raw material content of embodiment (i) in that it contains phosphorus sulfide, lithium halide and elemental halogen as raw materials. In addition to these raw materials, the raw materials exemplified as the raw material content of the above embodiment (i) can be used.
[0354] The blending ratio of the raw materials in the embodiment (ii) can be the same as the blending ratio of the raw materials described in the above embodiment (i). For example, in the above embodiment (i), when lithium sulfide, elemental sulfur, phosphorus pentasulfide and lithium halide are used, the ratio of lithium sulfide to the total of lithium sulfide and phosphorus pentasulfide is an embodiment containing elemental sulfur, but it can also be applied to the embodiment (ii) preferably not containing elemental sulfur. By adopting such a blending ratio, it is easy to obtain the preferred crystal structure of the sulfide solid electrolyte obtained by the manufacturing method of this embodiment, that is, the sulfide crystal lithium superion conductor region II type crystal structure, the argyrodite type crystal structure.
[0355] (First solvent)
[0356] In implementation mode (ii), as the first solvent used for mixing the above-mentioned raw materials, a solvent different from the second solvent can be used due to its relationship with the above-mentioned second solvent. In addition, a hydrocarbon solvent other than the hydrocarbon solvent used as the second solvent can be used, and a solvent containing heteroatoms is preferably used, which is the same as the above-mentioned implementation mode (i).
[0357] In embodiment (ii), among the solvents containing heteroatoms, alcohol solvents and ether solvents are preferred. Alcohol solvents and ether solvents can be used alone or in combination, and alcohol solvents and ether solvents are particularly preferred. As these solvents, the same solvents as those described in embodiment (i) above can be cited.
[0358] (1-1 solvent and 1-2 solvent)
[0359] In the embodiment (ii), as the first solvent used when mixing the raw materials, it is preferred to mix the raw material content in an ether solvent (1-1 solvent), and then add an alcohol solvent (1-2 solvent) to mix. In the case of using a mixed solvent containing multiple solvents as the first solvent, by using the 1-1 solvent and the 1-2 solvent separately, the separation and loss of various raw materials such as lithium sulfide, phosphorus sulfide, and lithium halide, which are preferably used as raw materials, can be suppressed.
[0360] When the first solvent includes an alcohol solvent and an ether solvent, the 1-1st solvent is preferably an ether solvent, and the 1-2nd solvent is preferably an alcohol solvent.
[0361] As the first-1 solvent, in addition to ether solvents, among solvents containing heteroatoms such as oxygen atoms and nitrogen atoms, ester solvents and amine solvents can also be preferably used. Among the above, ether solvents are preferred. Among ether solvents, alicyclic ethers are preferred, and tetrahydrofuran is particularly preferred.
[0362] The usage amount of the 1-1 solvent is preferably 100 mL or more, more preferably 200 mL or more, further preferably 350 mL or more, further preferably 450 mL or more, relative to 100 g of the raw material content, and the upper limit is preferably 1000 mL or less, more preferably 850 mL or less, further preferably 700 mL or less, further preferably 550 mL or less.
[0363] As the first-second solvent, an alcohol solvent is preferred. In this case, an aliphatic alcohol is preferred, a primary aliphatic alcohol is more preferred, methanol and ethanol are further preferred, and ethanol is particularly preferred.
[0364] The usage amount of the 1-2 solvent is preferably 200 mL or more, more preferably 400 mL or more, further preferably 700 mL or more, further preferably 900 mL or more relative to 100 g of the raw material content, and the upper limit is preferably 3000 mL or less, more preferably 2000 mL or less, further preferably 1700 mL or less, further preferably 1500 mL or less.
[0365] In embodiment (ii), similarly to embodiment (i), as a solvent other than the first solvent, hydrocarbon solvents such as aliphatic hydrocarbon solvents, alicyclic hydrocarbon solvents, aromatic hydrocarbon solvents, etc. exemplified as the second solvent may be used.
[0366] (mix)
[0367] Mixing of the raw material-containing substance with the first solvent in the embodiment (ii) can be performed by the same method as the mixing in the above-mentioned embodiment (i).
[0368] As described above, when the first solvent is divided into the 1-1 solvent and the 1-2 solvent and used, if the raw material content is mixed in the 1-1 solvent, a mixture is obtained as described above, and the raw material content is not completely dissolved. In the mixture, each raw material contained in the raw material content is maintained in a state of bonding with each other and the solvent, and by subsequently adding the 1-2 solvent for mixing, it is dissolved while maintaining a loose bond with the 1-1 solvent, and a solution containing an electrolyte precursor is obtained.
[0369] When the 1-1 solvent and the 1-2 solvent are used separately, the mixing conditions of the raw material content in the 1-1 solvent are not particularly limited as temperature conditions, and are usually -10 to 100° C., preferably 0 to 80° C., more preferably 10 to 70° C., and further preferably 20 to 60° C. In addition, the mixing time is usually 0.1 to 500 hours, and from the viewpoint of more efficiently and in larger quantities to prepare the reaction product, it is preferably 1 to 400 hours, more preferably 3 to 300 hours, further preferably 5 to 200 hours, and further preferably 10 to 100 hours.
[0370] As the mixing conditions when adding the first-second solvent for mixing, the temperature conditions are not particularly limited, and are, for example, usually -10 to 100° C., preferably 0 to 80° C., more preferably 10 to 70° C., and further preferably 20 to 60° C. In addition, the mixing time is usually 1 minute to 100 hours, and from the viewpoint of more efficiently and in larger quantities to prepare the solid electrolyte precursor, it is preferably 3 minutes to 80 hours, more preferably 5 minutes to 50 hours, further preferably 10 minutes to 10 hours, and further preferably 20 minutes to 1 hour.
[0371] [Obtaining electrolyte precursor]
[0372] In embodiment (ii), after obtaining a solution containing an electrolyte precursor by the above mixing, the solvent is removed from the solution to obtain an electrolyte precursor. The electrolyte precursor can be obtained by removing the solvent from the solution, for example, by a method using drying as in embodiment (i).
[0373] In addition, the "obtaining an electrolyte precursor" in embodiment (ii) can be performed in the same manner as the above embodiment (i) through the same operation as the "first heating" in the "heating" in embodiment (i), or can be performed by dividing it into "first heating-1" and "first heating-2".
[0374] [Heating treatment while supplying hydrogen sulfide]
[0375] In embodiment (ii), it is preferred to include: before heating, heating the electrolyte precursor while supplying hydrogen sulfide. Heating the electrolyte precursor while supplying hydrogen sulfide (hereinafter sometimes referred to as "heat treatment") can be performed after the electrolyte precursor is obtained by removing the solvent from the solution containing the electrolyte precursor. In addition, from the viewpoint of suppressing the quality reduction caused by the residue of lithium alcoholate, it is preferably performed before heating.
[0376] Therefore, the heat treatment is preferably performed after obtaining the electrolyte precursor and before heating, and before or after contacting with the second solvent.
[0377] The heating treatment is performed while supplying hydrogen sulfide.
[0378] The supply of hydrogen sulfide may be carried out by supplying hydrogen sulfide alone or by diluting hydrogen sulfide with an inert gas such as nitrogen or argon. When hydrogen sulfide is supplied by diluting with an inert gas, the content of hydrogen sulfide is preferably 5% by volume or more, more preferably 10% by volume or more, and further preferably 20% by volume or more. The upper limit is less than 100% by volume, preferably 90% by volume or less, more preferably 80% by volume or less, and further preferably 70% by volume or less.
[0379] The heating temperature of the heat treatment cannot be uniformly specified because it can be changed according to the types of the first and second solvents and the desired crystal structure, but it is preferably set to a temperature lower than the heating temperature in the heating described later, preferably 120° C. or higher, 130° C. or higher, 150° C. or higher, 250° C. or higher, 350° C. or higher, or 400° C. or higher, and as an upper limit, it can be preferably selected from a temperature range of 700° C. or lower, 600° C. or lower, 500° C. or lower, 450° C. or lower, 350° C. or lower, 250° C. or lower, 200° C. or lower, or 160° C. or lower. In addition, a range of 250° C. or higher as a lower limit and 200° C. or lower as an upper limit is described, but of course, a range of 250° C. or higher and 200° C. or lower cannot be adopted.
[0380] The time for the heat treatment is usually 1 minute to 10 hours, preferably 10 minutes to 8 hours, more preferably 30 minutes to 6 hours, and even more preferably 30 minutes to 2 hours.
[0381] During the heat treatment, the heating temperature may be kept constant, or the temperature may be increased, decreased, or a combination thereof.
[0382] For example, the solid electrolyte precursor can be placed in a furnace at room temperature (20° C.) and the temperature in the furnace can be raised to a firing temperature described below for heat treatment. Alternatively, the solid electrolyte precursor can be placed in a furnace set to a predetermined heating temperature for heat treatment.
[0383] The supply amount of hydrogen sulfide is preferably 0.01 Nm / 100 g of the raw material content. 3 / h or more, more preferably 0.03Nm 3 / h or more, more preferably 0.05Nm 3 / h or more, more preferably 0.08Nm 3 / h or more, and the upper limit is preferably 1.0 Nm 3 / h or less, more preferably 0.8Nm 3 / h or less, more preferably 0.6Nm 3 / h or less, more preferably 0.4Nm 3 When hydrogen sulfide is diluted with an inert gas and supplied, it may be supplied so that the supply amount of hydrogen sulfide is within the above range.
[0384] 〔Heating〕
[0385] In the embodiment (ii), heating is also included. In the embodiment (ii), the second solvent can be removed, a sulfide solid electrolyte can be formed, a sulfide solid electrolyte can be crystallized, and the like can be performed by heating.
[0386] The heating temperature varies depending on the type of the second solvent and the desired crystal structure and cannot be generally specified, but is preferably appropriately selected from the range of 20° C. to 500° C. as described above.
[0387] In embodiment (ii), as the heating temperature during heating, as described above, it can be selected according to the type of the second solvent and the desired crystal structure, preferably 150°C or more, 170°C or more, 200°C or more, 250°C or more, 350°C or more, 400°C or more, and as an upper limit, it can be preferably selected from a temperature range of 700°C or less, 600°C or less, 500°C or less, 450°C or less, 350°C or less, 250°C or less, 200°C or less, or 180°C or less. In addition, the heating temperature refers to the highest temperature during heating. In addition, a range of 250°C or more as a lower limit and 200°C or less as an upper limit is described, but of course, a range of 250°C or more and 200°C or less cannot be adopted.
[0388] Furthermore, when heating is performed, it is preferably a temperature higher than the heating temperature during the heat treatment.
[0389] The heating time is usually 1 minute to 10 hours, preferably 10 minutes to 8 hours, more preferably 30 minutes to 6 hours, and further preferably 1 hour to 5 hours. In addition, the firing time refers to the time for maintaining the heating temperature for firing. In the manufacturing method of the present embodiment, the firing is preferably maintained at a constant temperature with the above-mentioned firing time.
[0390] In the embodiment (ii), the heating may be performed continuously with the above-mentioned heating treatment, the heating may be performed while supplying hydrogen sulfide used in the heating treatment, or the heating may be performed while stopping the supply of hydrogen sulfide.
[0391] Typical specific examples of heat treatment and heating include:
[0392] (a) placing an electrolyte precursor in a furnace at room temperature (20° C.), heating the furnace while supplying hydrogen sulfide and raising the temperature in the furnace to the above-mentioned heating temperature, and then firing the precursor at the heating temperature while supplying hydrogen sulfide or stopping the supply of hydrogen sulfide;
[0393] (b) placing an electrolyte precursor in a furnace set to a predetermined heating temperature and heating the electrolyte precursor while supplying hydrogen sulfide, placing the electrolyte precursor after the heat treatment in a furnace set to a heating temperature during heating and heating the electrolyte precursor while supplying hydrogen sulfide, or heating the electrolyte precursor without supplying hydrogen sulfide;
[0394] (c) The electrolyte precursor is placed in a furnace set to a predetermined heating temperature, and heat-treated while supplying hydrogen sulfide. Then, the temperature is raised from the heating temperature of the heat treatment to the heating temperature during heating while supplying hydrogen sulfide or stopping the supply of hydrogen sulfide to perform firing.
[0395] In the embodiment (ii), as in the above embodiment (i), multi-stage heating may be performed as in the first heating and the second heating. In this case, the first heating may be performed as "first heating-1" and "first heating-2", and the second heating may be performed as "second heating-1" and "second heating-2".
[0396] (Sulfide solid electrolyte)
[0397] In the embodiment (ii) of the manufacturing method of the present embodiment, an amorphous sulfide solid electrolyte or a crystalline sulfide solid electrolyte is generated by performing the above-mentioned heat treatment or heating. Whether an amorphous sulfide solid electrolyte or a crystalline sulfide solid electrolyte is generated can be adjusted by the heating temperature when performing the heat treatment or heating. That is, it can be adjusted by setting a temperature higher or lower than the temperature (crystallization temperature) for producing a crystalline sulfide solid electrolyte having a desired crystal structure.
[0398] The amorphous sulfide solid electrolyte and the crystalline sulfide solid electrolyte obtained in the embodiment (ii) are the same as the amorphous sulfide solid electrolyte and the crystalline sulfide solid electrolyte explained as the solid electrolyte obtained in the above embodiment (i).
[0399] (use)
[0400] The sulfide solid electrolyte obtained by the production method of this embodiment suppresses the increase of particle size and the expansion of particle size distribution, has high ion conductivity, and has excellent battery performance. Therefore, it is suitable for lithium ion batteries, especially all-solid batteries.
[0401] The sulfide solid electrolyte obtained by the production method of this embodiment can be used for the positive electrode layer, the negative electrode layer, or the electrolyte layer. In addition, each layer can be produced by a known method.
[0402] In addition, the battery preferably uses a current collector in addition to the positive electrode layer, the electrolyte layer and the negative electrode layer, and the current collector can use a known current collector. For example, a layer obtained by coating a substance that reacts with the solid electrolyte such as Au, Pt, Al, Ti or Cu can be used.
[0403] Example
[0404] Next, the present invention will be specifically described by way of examples, but the present invention is not limited to these examples at all.
[0405] (Measurement of average particle size)
[0406] The particle size distribution when the cumulative volume percentage was 50% (D 50 ), which is taken as the average particle size. In addition, the arithmetic standard deviation of the average particle size is calculated.
[0407] (Measurement of powder XRD diffraction)
[0408] Powder X-ray diffraction (XRD) measurements were performed as follows.
[0409] The powder of the sulfide solid electrolyte obtained in the examples and comparative examples was filled into a groove with a diameter of 20 mm and a depth of 0.2 mm and flattened with glass to prepare a sample. The sample was sealed with a kapton film for XRD and measured under the following conditions in a manner that it was not in contact with air.
[0410] Measuring device: D2 PHASER, manufactured by Bruker Corporation
[0411] Tube voltage: 30kV
[0412] Tube current: 10mA
[0413] X-ray wavelength: Cu-Kα ray
[0414] Optical system: Concentration method
[0415] Slit configuration: Sola slit 4°, divergence slit 1mm, Kβ filter (Ni plate)
[0416] Detector: Semiconductor detector
[0417] Measuring range: 2θ = 10-60 degrees
[0418] Step width, scanning speed: 0.05deg, 0.05deg / second
[0419] (Measurement of ionic conductivity)
[0420] In this example, the measurement of ion conductivity was performed as follows.
[0421] The crystalline sulfide solid electrolytes obtained in the examples and comparative examples were formed into a 10 mm diameter (cross-sectional area S: 0.785 cm 2 ), round particles with a height (L) of 0.1 to 0.3 cm are used to make a sample. The top and bottom of the sample are taken as electrode terminals, and the AC impedance method is used for measurement at 25°C (frequency range: 5 MHz to 0.5 Hz, amplitude: 10 mV) to obtain a Cole-Cole plot. Near the right end of the arc observed in the high-frequency side area, the real part Z'(Ω) at the point where -Z"(Ω) is the smallest is taken as the bulk resistance R(Ω) of the electrolyte, and the ionic conductivity σ(S / cm) is calculated according to the following formula.
[0422] R=ρ(L / S)
[0423] σ=1 / ρ
[0424] (Example 1)
[0425] In a glove box under an argon atmosphere, 0.2546 g of lithium sulfide, 0.3241 g of phosphorus pentasulfide and 0.3554 g of elemental sulfur were mixed using a mortar and introduced into a 100 ml reaction tank (reaction tank 1) together with a stirrer. Similarly, 0.1236 g of lithium chloride and 0.1520 g of lithium bromide were mixed using a mortar and introduced into a 100 ml reaction tank (reaction tank 2) different from the above together with a stirrer. Under a nitrogen atmosphere, 14.94 mL of a mixed solvent of ethanol (EtOH), tetrahydrofuran (THF) and acetonitrile (ACN) (the total amount of tetrahydrofuran (THF) and acetonitrile (ACN) was 237.1 parts by volume relative to 1.0 part by volume of ethanol (EtOH), ethanol:tetrahydrofuran:acetonitrile = 0.0084:1:1 (volume ratio)) was added to reaction tank 1 as the first solvent, and the mixture was stirred and mixed for 10 minutes using a magnetic stirrer. Next, the solution in reaction tank 1 was added to reaction tank 2, and the mixture was further stirred and mixed for 10 minutes using a magnetic stirrer.
[0426] Next, the solvent was removed from the solution containing the electrolyte precursor by using a vacuum pump and an oil bath to obtain an electrolyte precursor.
[0427] 30 mL of toluene (second solvent) was added to the obtained electrolyte precursor at room temperature (20°C), and the mixture was stirred for 1 hour using a magnetic stirrer (rotation speed: 600 rpm). A glass filter (particle retention capacity: 1.6 μm) was used under a nitrogen atmosphere to obtain a powder of the electrolyte precursor in contact with the second solvent.
[0428] The obtained powder of the electrolyte precursor was heated under reduced pressure at room temperature (20°C) for 1 hour (first heating-1) and under reduced pressure at 130°C for 1 hour (first heating-2) using a vacuum pump and an oil bath. Furthermore, the powder obtained by the first heating was heated at 250°C in a nitrogen atmosphere for 1 hour (second heating-1), and further heated at 430°C in a nitrogen atmosphere for 8 hours (second heating-2) to obtain a powder.
[0429] The powder obtained after the second heating was subjected to powder XRD diffraction measurement. The X-ray diffraction spectrum is shown in Figure 1 .
[0430] The average particle diameter of the powder before contacting with the second solvent (hereinafter referred to as "powder 1") and the powder obtained after the second heating (hereinafter referred to as "powder 2") were measured to obtain the average particle diameter (D 50 ), arithmetic standard deviation. In addition, the ion conductivity of the powder obtained by heating at 430° C. in Example 1 was measured and found to be 5.5 mS / cm.
[0431] (Examples 2 to 5)
[0432] Powders of Examples 2 to 5 were obtained in the same manner as in Example 1 except that the drying conditions for obtaining the electrolyte precursor, the temperature conditions for contacting the electrolyte precursor with the second solvent, and the presence or absence of stirring were set to the conditions shown in Table 1.
[0433] The powder obtained after the second heating was subjected to powder XRD diffraction measurement. The X-ray diffraction spectrum is shown in Figures 2 to 5 .
[0434] The average particle size of powder 1 and powder 2 was measured to obtain the average particle size (D 50 ), arithmetic standard deviation. In addition, the ion conductivity of the powders obtained by heating at 430° C. in Examples 2 to 5 was measured. The above results are shown in Table 1.
[0435] (Comparative Example 1)
[0436] A powder was obtained in the same manner as in Example 1, except that the electrolyte precursor and the second solvent were not brought into contact and the first heating was not performed. Here, "powder 1" is a powder that has been dried to obtain an electrolyte precursor.
[0437] The powder obtained after the second heating was subjected to powder XRD diffraction measurement. The X-ray diffraction spectrum is shown in Figure 6 .
[0438] The average particle size of powder 1 and powder 2 was measured to obtain the average particle size (D 50 ), arithmetic standard deviation. In addition, the ion conductivity of the powder obtained by heating at 430° C. in Comparative Example 1 was measured. The above results are shown in Table 1.
[0439] [Table 1]
[0440] Table 1
[0441]
[0442] In Tables 1 to 3, the average particle diameter ratio indicates the ratio of the average particle diameters of the powder before and after heating, and is an index for understanding the presence or absence of granulation due to heating. The closer it is to 1.0, the smaller the degree of granulation due to heating.
[0443] The standard deviation ratio represents the ratio of the standard deviation of the average particle diameter of the powder before and after heating, and is an index for understanding the width of the particle size distribution caused by heating. The closer it is to 1.0, the smaller the change in the particle size distribution caused by heating.
[0444] As shown in Table 1, it was confirmed that the average particle diameter ratio of Examples 1 to 5 was better than that of Comparative Example 1, and the effect of suppressing the increase of particle diameter was excellent. In addition, the standard deviation ratio was also generally excellent, so it was confirmed that the sulfide solid electrolyte obtained by the production method of this embodiment suppressed the increase of particle diameter and the expansion of particle size distribution.
[0445] According to Examples 1, 2, and 5, it was confirmed that drying by heating in the same manner as the first heating before contact with the second solvent was effective in suppressing the increase in particle size and the expansion of particle size distribution. Example 3 is an example in which the drying conditions in Example 1 are changed to room temperature (20° C.), and it was confirmed that the particle size can be reduced and the increase in particle size can be suppressed. In addition, according to Example 4, it was confirmed that by contacting with the second solvent under higher temperature conditions, the particle size can be reduced and the increase in particle size can be suppressed, while the particle size distribution can be reduced and the change in particle size distribution can be reduced.
[0446] From the comparison between Examples 1 to 4 and Comparative Example 1, it can be seen that the average particle size can be reduced by stirring the electrolyte precursor and the second solvent during contact. On the other hand, from the comparison between Example 5 in which the electrolyte precursor and the second solvent were contacted without stirring and Comparative Example 1, it can be seen that the average particle size becomes larger when the electrolyte precursor and the second solvent are contacted without stirring. It is believed that the aggregation of the electrolyte precursor is suppressed or reduced by stirring the electrolyte precursor and, as a result, the average particle size of the sulfide solid electrolyte obtained by heating also becomes smaller.
[0447] As can be seen from the above, the average particle size can be adjusted by the presence or absence of stirring and the degree of stirring.
[0448] Furthermore, it was confirmed that the ion conductivity of the sulfide solid electrolytes of Examples was 5.5 to 8.1 mS / cm, which was high. This is considered to be because the sulfide solid electrolytes of Examples had an argyrodite-type crystal structure that exhibited high ion conductivity, as described later.
[0449] like Figures 1 to 5 As shown, the powders obtained by heating at 430°C in Examples 1 to 5 have peaks at 2θ=15.5°, 18.0°, 25.0°, 30.0°, 31.4°, 45.3°, 47.0° and 52.0°, and thus it was confirmed that they were crystalline sulfide solid electrolytes having an argyrodite-type crystal structure.
[0450] (Example 6)
[0451] In a glove box under an argon atmosphere, 60.19 g of lithium sulfide, 76.63 g of phosphorus pentasulfide and 84.02 g of elemental sulfur were mixed using a mixer and introduced into a 5-liter reaction tank (reaction tank 1-1 and 1-2) in half with a stirrer. Similarly, 14.61 g of lithium chloride and 17.96 g of lithium bromide were introduced into a 5-liter reaction tank (reaction tank 2) different from the above in half with a stirrer. Under a nitrogen atmosphere, 3546 mL of a mixed solvent of ethanol (EtOH), tetrahydrofuran (THF) and acetonitrile (ACN) (the total amount of tetrahydrofuran (THF) and acetonitrile (ACN) was 239.0 parts by volume relative to 1.0 part by volume of ethanol (EtOH), ethanol:tetrahydrofuran:acetonitrile = 0.0084:1:1 (volume ratio)) was added to reaction tanks 1-1 and 1-2 in half, and the mixture was stirred and mixed using a magnetic stirrer for 10 minutes. Next, the solutions in reaction tanks 1-1 and 1-2 were added to reaction tank 2, and the mixture was further stirred and mixed for 1 hour using a magnetic stirrer.
[0452] Next, the obtained solution containing the electrolyte precursor was spray dried using a spray drying apparatus ("CNL-3 (model)", manufactured by Ohgawara Chemical Industry Co., Ltd.) at a spray pressure of 0.30 MPa and an apparatus inlet temperature of 150° C. to obtain an electrolyte precursor. The obtained electrolyte precursor was subjected to the same operation as in Example 1 from contact with the second solvent to the second heating to obtain a powder of Example 6.
[0453] The powder obtained after the second heating was subjected to powder XRD diffraction measurement. The X-ray diffraction spectrum is shown in Figure 7 .
[0454] The average particle size of powder 1 and powder 2 was measured to obtain the average particle size (D 50 ), arithmetic standard deviation. In addition, the ion conductivity of the powder obtained by heating at 430° C. in Example 6 was measured. The results are shown in Table 2.
[0455] (Comparative Example 2)
[0456] A powder was obtained in the same manner as in Example 6, except that the electrolyte precursor was not brought into contact with the second solvent and the first heating was not performed. Here, "powder 1" is a powder that has been dried to obtain an electrolyte precursor.
[0457] The powder obtained after the second heating was subjected to powder XRD diffraction measurement. The X-ray diffraction spectrum is shown in Figure 8 .
[0458] The average particle size of powder 1 and powder 2 was measured to obtain the average particle size (D 50 ), arithmetic standard deviation. In addition, the ion conductivity of the powder obtained by heating at 430° C. in Comparative Example 2 was measured. The above results are shown in Table 2.
[0459] [Table 2]
[0460] Table 2
[0461]
[0462] As shown in Table 2, the average particle size ratio and standard deviation ratio of Example 6 are superior to those of Comparative Example 2, and it is confirmed that the sulfide solid electrolyte obtained by the production method of this embodiment suppresses the increase in particle size and the expansion of particle size distribution.
[0463] Furthermore, it was confirmed that the ion conductivity of the sulfide solid electrolyte of Example 6 was as high as 2.1 mS / cm. This is considered to be because the sulfide solid electrolyte of the example has an argyrodite-type crystal structure that exhibits high ion conductivity, as described later.
[0464] According to the results of Examples 1 to 5 and Example 6, it is also confirmed that when the electrolyte precursor is obtained by removing the solvent from the solution containing the electrolyte precursor, the average particle size and the arithmetic standard deviation will also change according to the drying method. For example, Example 1 using vacuum drying and Example 6 using spray drying are compared under the same conditions other than the drying method. Since the average particle size and arithmetic standard deviation of Example 6 using spray drying are smaller than those of Example 1, it can be seen that the average particle size and the arithmetic standard deviation can be reduced by using spray drying. That is, it can be seen that compared with other embodiments, the average particle size can be reduced and the arithmetic standard deviation can be reduced (reduced particle size distribution).
[0465] In addition, if Figure 7 As shown, the powder obtained by heating at 430°C in Example 6 has peaks at 2θ=15.5°, 18.0°, 25.0°, 30.0°, 31.4°, 45.3°, 47.0° and 52.0°, thus confirming that it is a crystalline sulfide solid electrolyte having an argyrodite-type crystal structure.
[0466] (Example 7)
[0467] Under a nitrogen atmosphere, 0.5960g of lithium sulfide, 0.7588g of phosphorus pentasulfide, 0.2894g of lithium chloride and 0.3558g of lithium bromide were introduced into a reaction tank (capacity: 100mL) as raw material contents. A stirring bar was introduced, and 10mL of tetrahydrofuran was added while stirring with a stirrer. Mixing was performed at room temperature (20°C) for 24 hours (rotation speed: 300rpm) to obtain a mixture containing the above-mentioned raw material contents, reaction products (including Li3PS4) and tetrahydrofuran (1-1 solvent). Then, 30mL of ethanol (1-2 solvent) was supplied, and mixing was further performed for 1 hour at room temperature (20°C) to prepare a solution containing an electrolyte precursor. The obtained solution was dried at room temperature and vacuum for 1 hour, and then dried at 130°C for 1 hour to remove the solvent from the solution containing the electrolyte precursor to obtain an electrolyte precursor.
[0468] 30 mL of toluene (second solvent) was added to 1.2 g of the obtained electrolyte precursor at room temperature (20°C), and the mixture was stirred for 1 hour using a magnetic stirrer (rotation speed: 600 rpm). A glass filter (particle retention capacity: 1.6 μm) was used under a nitrogen atmosphere to obtain a powder of the electrolyte precursor obtained by contact with the second solvent.
[0469] The obtained powder of the electrolyte precursor was heated under reduced pressure at room temperature (20° C.) for 1 hour using a vacuum pump and an oil bath, and was heated under reduced pressure at 130° C. for 1 hour. Next, the obtained powder was heated at 250° C. in a nitrogen atmosphere for 1 hour, and further heated at 430° C. in a nitrogen atmosphere for 8 hours to obtain a powder.
[0470] The powder obtained after heating at 430°C was subjected to powder XRD diffraction measurement. The X-ray diffraction spectrum is shown in Fig. 9 .
[0471] The average particle diameter of the powder before contact with the second solvent (hereinafter referred to as "powder 1") and the powder obtained after heating at 430°C (hereinafter referred to as "powder 2") was measured to obtain the average particle diameter (D 50 ), arithmetic standard deviation. In addition, the ion conductivity of the powder obtained by heating at 430° C. in Example 7 was measured. The above results are shown in Table 3.
[0472] (Example 8)
[0473] A powder was obtained in the same manner as in Example 7 except that the amounts of the raw material content and the solvent used in obtaining the solid electrolyte precursor were changed to 0.6 times, and the drying conditions were changed to the conditions shown in Table 2.
[0474] The powder obtained after heating at 430°C was subjected to powder XRD diffraction measurement. The X-ray diffraction spectrum is shown in Fig.10 .
[0475] The average particle size of powder 1 and powder 2 was measured to obtain the average particle size (D 50 ), and arithmetic standard deviation. In addition, the ion conductivity of the powder obtained by heating at 430° C. was measured. The above results are shown in Table 3.
[0476] (Comparative Example 3)
[0477] A powder was obtained in the same manner as in Example 7 except that drying of the electrolyte precursor and contact of the electrolyte precursor with the second solvent were not performed. Here, "Powder 1" is a powder before heating at room temperature (20°C) under reduced pressure for 1 hour.
[0478] The powder obtained after heating at 430°C was subjected to powder XRD diffraction measurement. The X-ray diffraction spectrum is shown in Fig.11 .
[0479] The average particle size of powder 1 and powder 2 was measured to obtain the average particle size (D 50), and arithmetic standard deviation. In addition, the ion conductivity of the powder obtained by heating at 430° C. was measured. The above results are shown in Table 3.
[0480] [Table 3]
[0481] Table 3
[0482]
[0483] As shown in Table 3, the average particle diameter ratio and standard deviation ratio of Examples 7 and 8 are superior to those of Comparative Example 3, and it is confirmed that the sulfide solid electrolyte obtained by the production method of this embodiment suppresses the increase of particle diameter and the expansion of particle size distribution. In addition, the average particle diameter and standard deviation of Examples 7 and 8 are smaller than those of Comparative Example 3, and it is confirmed that it is effective not only in suppressing the increase of particle diameter and the expansion of particle size distribution, but also in reducing particle diameter and particle size distribution.
[0484] In addition, it was confirmed that the ion conductivity was 1.7 and 3.9 mS / cm, both of which were high.
[0485] like Fig. 9 and 10 As shown, the powders obtained by heating at 250°C and 430°C in Examples 7 and 8 have peaks at 2θ=15.5°, 18.0°, 25.0°, 30.0°, 31.4°, 45.3°, 47.0° and 52.0°, thus confirming that they are crystalline sulfide solid electrolytes having an argyrodite-type crystal structure.
[0486] Industrial Applicability
[0487] According to the method for producing a sulfide solid electrolyte of the present embodiment, it is possible to efficiently provide a sulfide solid electrolyte having high ion conductivity with suppressed increase in particle size and expansion of particle size distribution. The sulfide solid electrolyte obtained by the production method of the present embodiment is suitable for use in lithium ion batteries, particularly batteries used in information-related devices or communication devices such as personal computers, cameras, and mobile phones, and in particular all-solid batteries.
Claims
1. A method for producing a sulfide solid electrolyte, characterized in that: include: A raw material containing a plurality of raw materials is mixed in a first solvent to obtain a solution containing an electrolyte precursor, wherein the raw material contains at least one atom selected from lithium atoms, phosphorus atoms, sulfur atoms, and halogen atoms; removing the solvent from the solution to obtain an electrolyte precursor; contacting the electrolyte precursor with a second solvent; and Then heating, The second solvent is different from the first solvent and is a hydrocarbon solvent.
2. The method for producing a sulfide solid electrolyte according to claim 1, wherein: The hydrocarbon solvent is at least one organic solvent selected from aliphatic hydrocarbon solvents, alicyclic hydrocarbon solvents, and aromatic hydrocarbon solvents.
3. The method for producing a sulfide solid electrolyte according to claim 1 or 2, wherein: The solubility of the lithium halide in the hydrocarbon solvent at 25° C. is 0.5 mass % or less.
4. The method for producing a sulfide solid electrolyte according to any one of claims 1 to 3, wherein: The hydrocarbon solvent is an aromatic hydrocarbon solvent.
5. The method for producing a sulfide solid electrolyte according to claim 4, wherein: The aromatic hydrocarbon solvent is alkylbenzene.
6. The method for producing a sulfide solid electrolyte according to claim 5, wherein: The alkylbenzene has an alkyl group having 1 to 4 carbon atoms.
7. The method for producing a sulfide solid electrolyte according to any one of claims 1 to 6, wherein: The amount of the second solvent used in the contacting is 50 parts by mass or more and 10,000 parts by mass or less relative to 100 parts by mass of the electrolyte precursor.
8. The method for producing a sulfide solid electrolyte according to any one of claims 1 to 7, wherein: The contacting is performed at least once.
9. The method for producing a sulfide solid electrolyte according to any one of claims 1 to 8, wherein: The raw material contains elemental sulfur.
10. The method for producing a sulfide solid electrolyte according to claim 9, wherein: The first solvent is an organic solvent containing at least one atom selected from oxygen atoms and nitrogen atoms.
11. The method for producing a sulfide solid electrolyte according to claim 10, wherein: The organic solvent includes at least one organic solvent selected from alcohol solvents, ether solvents, and nitrile solvents.
12. The method for producing a sulfide solid electrolyte according to any one of claims 9 to 11, characterized in that: The heating temperature during the heating is 20° C. or higher and 500° C. or lower.
13. The method for producing a sulfide solid electrolyte according to any one of claims 9 to 12, wherein: The amount of the elemental sulfur used is 0.5 mol or more relative to 1.0 mol of the lithium sulfide.
14. The method for producing a sulfide solid electrolyte according to any one of claims 1 to 8, wherein: The raw material contains lithium sulfide, phosphorus sulfide and at least one halogen atom-containing raw material selected from lithium halide and elemental halogen.
15. The method for producing a sulfide solid electrolyte according to any one of claims 1 to 8 and 14, wherein: The raw material contains no elemental sulfur.
16. The method for producing a sulfide solid electrolyte according to claim 14 or 15, wherein: include: Prior to the heating, the electrolyte precursor is subjected to a heat treatment while supplying hydrogen sulfide.
17. The method for producing a sulfide solid electrolyte according to any one of claims 14 to 16, wherein: The first solvent includes an alcohol solvent and an ether solvent.
18. The method for producing a sulfide solid electrolyte according to claim 17, wherein: When obtaining the solution containing the electrolyte precursor, the raw material-containing substances are mixed in an ether solvent, and then an alcohol solvent is added and mixed.
19. The method for producing a sulfide solid electrolyte according to any one of claims 14 to 18, wherein: The heating temperature during the heating is 150° C. or higher.
20. The method for producing a sulfide solid electrolyte according to any one of claims 1 to 19, wherein: The halogen atom is at least one atom selected from a chlorine atom, a bromine atom, and an iodine atom.
21. The method for producing a sulfide solid electrolyte according to any one of claims 1 to 20, wherein: A crystalline sulfide solid electrolyte having an argyrodite-type crystal structure or a sulfide crystalline lithium superion conductor region-type II crystal structure is produced.
Citation Information
Patent Citations
Solid sulfide electrolyte material, solid-state lithium battery, and method for manufacturing solid sulfide electrolyte material
JP2013016423A
Liquid solution for formation of a solid electrolyte-containing layer of all-solid type lithium secondary battery, all-solid type lithium secondary battery, and method for manufacturing the same
JP2014191899A
Process of manufacturing sulfide solid electrolyte
JP2014220051A
Sulfide solid electrolyte, and method of producing sulfide solid electrolyte
JP2015232965A
Method for producing solid electrolyte
JP2019169459A
Cited By
Liquid phase synthesis method of sulfide solid electrolyte and sulfide solid electrolyte
CN121651390A